Optical laminate, polarizing plate and image display device
By directly stacking two liquid crystal layers in the optical Raman sheet and coating the second layer with fluorine or silicon-containing light alignment polymer, the problem of insufficient durability and adhesion of the optical opposite-like layer in a high humidity and heat environment is solved, and better optical performance is achieved.
Patent Information
- Application Number
- JP2022554049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-29
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-09-29
AI Technical Summary
The existing optical Raman sheets exhibit poor durability in high humidity and heat environments, and insufficient adhesion between optical opposite-sex layers affects optical performance.
By directly stacking two liquid crystal layers in an optical Raman sheet, at least one layer exhibits an inverse wavelength dispersibility and coating a light alignment polymer containing fluorine or silicon on the surface of the second layer to optimize surface element ratio and improve adhesion.
The durability of the optical opposite-sex layer in a high humidity and heat environment is improved, and the adhesion between the first and second optical opposite-sex layers is enhanced, thereby improving the performance of the overall optical Raman sheet.
Smart Images

Figure 0007655931000001 
Figure 0007655931000002 
Figure 0007655931000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate, a polarizing plate, and an image display device. [Background technology]
[0002] Optical films such as optical compensation sheets and retardation films are used in various image display devices from the viewpoints of eliminating image coloration and widening the viewing angle. Stretched birefringent films have been used as optical films, but in recent years, optically anisotropic layers formed using liquid crystal compounds have been proposed in place of stretched birefringent films. When forming such an optically anisotropic layer, a photo-alignment film obtained by performing a photo-alignment treatment is sometimes used in order to align the liquid crystal compound.
[0003] For example, Patent Document 1 describes an embodiment in which a binder layer is formed using a specific photo-alignable polymer having a repeating unit containing a cleavable group that decomposes to generate a polar group by the action of at least one selected from the group consisting of light, heat, acid, and base, and an optically anisotropic layer is provided on top of the binder layer (see [Claim 1], [Claim 7] to [Claim 9], etc.), and Example 6 describes a method in which a binder layer (liquid crystal layer) is formed using photo-alignable polymer KH3 represented by the following formula, and an optically anisotropic layer is formed on top of the binder layer. [ka]
[0004] Furthermore, Comparative Example 3 of Patent Document 2 describes a method in which a binder layer (liquid crystal layer) is formed using a photoalignable polymer H2 represented by the following formula, and an optically anisotropic layer is formed thereon. [ka] [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2018 / 216812 [Patent Document 2] International Publication No. 2019 / 159707 Summary of the Invention [Problem to be solved by the invention]
[0006] The present inventors have investigated photoalignable polymers having fluorine atoms or silicon atoms among the photoalignable polymers specifically described in Patent Documents 1 and 2 and the like. Specifically, the inventors have studied an optical laminate having a liquid crystal layer (second optically anisotropic layer) formed using a composition containing a photoalignable polymer having fluorine atoms or silicon atoms and a liquid crystal compound, and a liquid crystal layer (first optically anisotropic layer) laminated directly on top of the second optically anisotropic layer, and have found that when at least one of the first optically anisotropic layer and the second optically anisotropic layer is an optically anisotropic layer exhibiting reverse wavelength dispersion, there is room for improvement in the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion, for example, when it is attached to a panel. Furthermore, the inventors have studied the above-mentioned optical laminate and found that there is room for improvement in the adhesion between the first optically anisotropic layer and the second optically anisotropic layer, depending on the type of photo-alignable polymer having fluorine atoms or silicon atoms.
[0007] Therefore, an object of the present invention is to provide an optical laminate having excellent wet heat durability in an optically anisotropic layer exhibiting reverse wavelength dispersion and excellent adhesion between a first optically anisotropic layer and a second optically anisotropic layer, as well as a polarizing plate and an image display device using the same. [Means for solving the problem]
[0008] As a result of intensive research by the inventors to achieve the above object, they have found that in an optical laminate in which a first optically anisotropic layer and a second optically anisotropic layer are directly laminated, the first optically anisotropic layer and the second optically anisotropic layer are both made of liquid crystal layers, and at least one of the first optically anisotropic layer and the second optically anisotropic layer exhibits reverse wavelength dispersion, by having a photoalignable polymer present on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer so that the element ratio of fluorine or silicon is a specific amount, the optically anisotropic layer exhibiting reverse wavelength dispersion has good wet heat durability and good adhesion between the first optically anisotropic layer and the second optically anisotropic layer, and have completed the present invention. That is, the present inventors have found that the above object can be achieved by the following configuration.
[0009] [1] An optical laminate comprising a first optically anisotropic layer and a second optically anisotropic layer directly laminated together, the first optically anisotropic layer and the second optically anisotropic layer are both made of liquid crystal layers; At least one of the first optically anisotropic layer and the second optically anisotropic layer exhibits reverse wavelength dispersion; a photoalignment polymer having a photoalignment group and a fluorine atom or a silicon atom is present on a surface of the second optically anisotropic layer on the side in contact with the first optically anisotropic layer; An optical laminate, wherein the element ratio of fluorine or silicon in the surface of the second optically anisotropic layer on the side in contact with the first optically anisotropic layer is 0.05 to 15.00 atomic %. [2] The optical laminate according to [1], wherein the photo-alignable group is a photo-alignable group that undergoes at least one of dimerization and isomerization by the action of light. [3] The optical laminate according to [1] or [2], wherein the photoalignment group is selected from the group consisting of a cinnamoyl group, an azobenzene group, a chalconyl group, and a coumarin group. [4] The optical laminate according to any one of [1] to [3], wherein the photoalignable polymer has a repeating unit represented by formula (A) described below. [5] The optical laminate according to any one of [1] to [4], wherein the photoalignable polymer has a partial structure represented by the following formula (1): *-(CF2) m -* ···(1) In the formula (1), * represents a bonding position, and m represents an integer of 2 to 20. [6] The optical laminate according to any one of [1] to [5], wherein the photoaligned polymer has a group represented by the following formula (2): *-(CF2) m -X (2) In the formula (2), * represents a bonding position, m represents an integer of 2 to 20, and X represents a hydrogen atom or a fluorine atom. [7] The optical laminate according to [6], wherein X in formula (2) represents a hydrogen atom. [8] The optical laminate according to any one of [1] to [4], wherein the photoaligned polymer has a group represented by the following formula (3): *-C(Y)(CF3)2···(3) In the formula (3), * represents a bonding position, and Y represents a hydrogen atom or a substituent. [9] The optical laminate according to any one of [1] to [8], wherein at least one of the first optically anisotropic layer and the second optically anisotropic layer is an optically anisotropic layer in which the orientation of a liquid crystal compound having any one of aromatic rings selected from the group consisting of groups represented by formulas (Ar-1) to (Ar-7) described later is fixed.
[10] The optical laminate according to any one of [1] to [9], wherein the first optically anisotropic layer is a positive A plate.
[11] The optical laminate according to any one of [1] to
[10] , wherein the second optically anisotropic layer is a positive C plate.
[12] A polarizing plate comprising the optical laminate according to any one of [1] to
[11] and a polarizer.
[13] An image display device comprising the optical laminate according to any one of [1] to
[11] or the polarizing plate according to
[12] . Effect of the Invention
[0010] According to the present invention, it is possible to provide an optical laminate having excellent wet heat durability of an optically anisotropic layer exhibiting reverse wavelength dispersion and excellent adhesion between a first optically anisotropic layer and a second optically anisotropic layer, as well as a polarizing plate and an image display device using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. The following description of the components may be based on representative embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In the present specification, each component may be used alone or in combination of two or more substances corresponding to each component. When two or more substances are used in combination for each component, the content of the component refers to the total content of the substances used in combination, unless otherwise specified. In addition, in this specification, "(meth)acrylate" is a notation representing "acrylate" or "methacrylate", "(meth)acryl" is a notation representing "acryl" or "methacryl", and "(meth)acryloyl" is a notation representing "acryloyl" or "methacryloyl". In addition, the bond direction of a divalent group (e.g., -O-CO-) described in this specification is not particularly limited. 1 -L 2 -L 3 " in the bond 2 When is -O-CO-, L 1 The position where it is bonded to the side is *1, L 3 If the position where the molecule is bonded to the side is *2, then L 2 may be *1-O-CO-*2 or *1-CO-O-*2.
[0012] [Optical laminate] The optical laminate of the present invention is an optical laminate in which a first optically anisotropic layer and a second optically anisotropic layer are directly laminated together. In addition, in the optical laminate of the present invention, the first optically anisotropic layer and the second optically anisotropic layer are both made of liquid crystal layers, and at least one of the first optically anisotropic layer or the second optically anisotropic layer exhibits reverse wavelength dispersion. Furthermore, in the optical laminate of the present invention, a photoalignable polymer having a photoalignable group and a fluorine atom or a silicon atom is present on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer, and the atomic ratio of fluorine or silicon on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer is 0.05 to 15.00 atomic %.
[0013] Here, an optically anisotropic layer exhibiting reverse wavelength dispersion refers to an optically anisotropic layer in which the in-plane retardation value Re(450) measured at a wavelength of 450 nm, the in-plane retardation value Re(550) measured at a wavelength of 550 nm, and the in-plane retardation value Re(650) measured at a wavelength of 650 nm satisfy the relationship Re(450)≦Re(550)≦Re(650). The in-plane retardation value is a value measured using an AxoScan OPMF-1 (manufactured by Optoscience) with light of a measuring wavelength. Specifically, by inputting the average refractive index ((Nx+Ny+Nz) / 3) and the film thickness (d(μm)) into the AxoScan OPMF-1, Slow axis direction (°) Re(λ)=R0(λ) Rth(λ)=((nx+ny) / 2-nz)×d is calculated. Note that R0(λ) is displayed as a numerical value calculated by AxoScan OPMF-1, and means Re(λ).
[0014] In the present invention, as described above, in a given optical laminate in which a first optically anisotropic layer and a second optically anisotropic layer are directly laminated, a photoalignable polymer is present on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer so that the atomic ratio of fluorine or silicon is 0.05 to 15.00 atomic %, thereby improving the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion and improving the adhesion between the first optically anisotropic layer and the second optically anisotropic layer. Although the details of this are not clear, the present inventors speculate as follows. First, as shown in Comparative Examples 1 and 3 described later, when the atomic ratio of fluorine or silicon in the surface of the second optically anisotropic layer on the side in contact with the first optically anisotropic layer is more than 15 atomic %, the adhesion between the first optically anisotropic layer and the second optically anisotropic layer is poor. This is believed to be because the coating property of the composition forming the first optically anisotropic layer is poor when the first optically anisotropic layer is formed directly on the second optically anisotropic layer. In addition, as shown in Comparative Examples 2 and 4 described later, when a photo-aligning polymer having a photo-aligning group and a fluorine atom or a silicon atom is not present on the surface of the second optically anisotropic layer on the side in contact with the first optically anisotropic layer, the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion is inferior. This is believed to be because the liquid crystal compound constituting the optically anisotropic layer exhibiting reverse wavelength dispersion, which has poorer wet heat durability, is decomposed due to the moisture in the system moving freely across the interface between the first optically anisotropic layer and the second optically anisotropic layer. Therefore, in the present invention, by having a photoalignable polymer present on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer so that the atomic ratio of fluorine or silicon is 0.05 to 15.00 atomic %, there is no effect on the coatability when forming the first optically anisotropic layer as an upper layer of the second optically anisotropic layer, and after the optical laminate is produced, the movement of moisture within the system is blocked by the fluorine atoms or silicon atoms present on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer, which is thought to improve the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion and the adhesion between the first optically anisotropic layer and the second optically anisotropic layer.
[0015] In the following, first, the second optically anisotropic layer having a photoalignable polymer will be described in detail, and then the first optically anisotropic layer as the upper layer will be described in detail.
[0016] [Second Optically Anisotropic Layer] The optical laminate of the present invention has a photoalignable polymer having a photoalignable group and a fluorine atom or silicon (hereinafter, formally abbreviated as "the photoalignable polymer of the present invention") present on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer. In the optical laminate of the present invention, the element ratio of fluorine or silicon in the surface of the second optically anisotropic layer on the side in contact with the first optically anisotropic layer is 0.05 to 15.00 atomic %. Here, the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer refers to the region from the surface of the second optically anisotropic layer opposite the first optically anisotropic layer, toward the first optically anisotropic layer, from a depth position corresponding to 80% of the total thickness of the second optical layer to a position that is the interface with the first optically anisotropic layer, hereinafter also abbreviated as "surface layer A". The presence of the photoalignable polymer in the surface layer A of the second optically anisotropic layer can be confirmed, for example, by time-of-flight secondary ion mass spectrometry (TOF-SIMS). For TOF-SIMS, the method described in "Surface Analysis Techniques Selection: Secondary Ion Mass Spectroscopy" edited by the Japan Surface Science Society, published by Maruzen Co., Ltd. (1999) can be adopted. Specifically, when a photo-alignable polymer having a photo-alignable group and a fluorine atom or a silicon atom is present on the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer, i.e., on the interface between the first optically anisotropic layer and the second optically anisotropic layer, both fragments derived from the photo-alignable group and fragments derived from units having fluorine atoms or silicon atoms will be detected at the same position near the interface. On the other hand, the atomic ratio of fluorine or silicon in the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer refers to an atomic ratio measured by the following procedure. First, a polyethylene terephthalate (PET) tape is attached to the surface of the first optically anisotropic layer opposite the second optically anisotropic layer, and the substrate of the optical laminate is peeled off (the first optically anisotropic layer and the second optically anisotropic layer are transferred). Next, the secondary ion intensity derived from fluorine or silicon in the second optically anisotropic layer is measured by TOF-SIMS while irradiating an ion beam from the surface of the second optically anisotropic layer opposite the first optically anisotropic layer. Next, the irradiation of the ion beam is stopped at a position where the intensity of secondary ions derived from fluorine or silicon is maximum in a region from a depth position corresponding to 80% of the total thickness of the second optical anisotropic layer toward the first optical anisotropic layer, from the surface of the second optical anisotropic layer opposite the first optical anisotropic layer, to a position which is the interface with the first optical anisotropic layer. The element ratio of fluorine or silicon is then calculated by X-ray photoelectron spectroscopy (XPS) for the area irradiated with the ion beam.
[0017] <Photo-aligned polymer> As described above, the photoalignable polymer of the present invention is a photoalignable polymer having a photoalignable group and a fluorine atom or silicon.
[0018] The photoalignable group is preferably a group that undergoes at least one of dimerization and isomerization by the action of light, because this improves the thermal stability and chemical stability of a monomer having the photoalignable group. Specific examples of the group that dimerizes by the action of light preferably include groups having a skeleton of at least one derivative selected from the group consisting of cinnamic acid derivatives, coumarin derivatives, chalcone derivatives, maleimide derivatives, and benzophenone derivatives. On the other hand, specific examples of groups that are isomerized by the action of light preferably include groups having a skeleton of at least one compound selected from the group consisting of an azobenzene compound, a stilbene compound, a spiropyran compound, a cinnamic acid compound, and a hydrazono-β-ketoester compound.
[0019] Of such photo-aligning groups, a photo-aligning group selected from the group consisting of a cinnamoyl group, an azobenzene group, a chalconyl group, and a coumarin group is preferred, because this provides better alignment (hereinafter referred to as "liquid crystal alignment") of the first optically anisotropic layer formed on the upper layer even with a small amount of exposure, and a cinnamoyl group is more preferred.
[0020] The photoalignable polymer of the present invention is preferably a polymer having a repeating unit containing a photoalignable group, and specifically, is preferably either a polymer having a repeating unit containing a fluorine atom or a silicon atom together with a photoalignable group, or a copolymer having a repeating unit containing a photoalignable group and a repeating unit containing a fluorine atom or a silicon atom.
[0021] As the repeating unit containing a photoalignable group, a repeating unit represented by the following formula (A) (hereinafter also abbreviated as "repeating unit A") is preferred because it provides good liquid crystal alignment properties. [ka]
[0022] In the above formula (A), R A1 represents a hydrogen atom or a substituent. Also, L A1 represents a single bond or a divalent linking group. Also, R A2 , R A3 , R A4 , R A5 and R A6 R each independently represents a hydrogen atom or a substituent. A2 , R A3 , R A4 , R A5 and R A6 Among these, two adjacent groups may be bonded to form a ring.
[0023] In the above formula (A), R A1 represents a hydrogen atom or a substituent. R A1The type of the substituent represented by one embodiment of the formula (1) is not particularly limited, and examples thereof include known substituents. Examples of the substituent include monovalent aliphatic hydrocarbon groups which may have an oxygen atom, and monovalent aromatic hydrocarbon groups which may have an oxygen atom, and more specifically, alkyl groups, alkenyl groups, alkynyl groups, aryl groups, alkoxy groups, aryloxy groups, acyl groups, acyloxy groups, and groups combining these groups. The above-mentioned substituents may be further substituted with a substituent. Of these substituents, an alkyl group having 1 to 12 carbon atoms is preferred, a linear alkyl group having 1 to 8 carbon atoms or a branched alkyl group having 3 to 8 carbon atoms is more preferred, and a methyl group is even more preferred.
[0024] In the above formula (A), L A1 represents a single bond or a divalent linking group. L A1 Examples of the divalent linking group represented by one embodiment of the formula (1) include a divalent hydrocarbon group which may have a substituent, a divalent heterocyclic group, -O-, -S-, -N(Q)-, -CO-, or a combination thereof. Q represents a hydrogen atom or a substituent. Examples of the divalent hydrocarbon group include divalent aliphatic hydrocarbon groups such as alkylene groups having 1 to 10 carbon atoms (preferably 1 to 5 carbon atoms), alkenylene groups having 1 to 10 carbon atoms, and alkynylene groups having 1 to 10 carbon atoms; and divalent aromatic hydrocarbon groups such as arylene groups. Examples of the divalent heterocyclic group include a divalent aromatic heterocyclic group, and specific examples thereof include a pyridylene group (pyridine-diyl group), a pyridazine-diyl group, an imidazole-diyl group, a thienylene group (thiophene-diyl group), and a quinolylene group (quinoline-diyl group). Examples of groups combining these include groups combining at least two or more selected from the group consisting of the above-mentioned divalent hydrocarbon groups, divalent heterocyclic groups, -O-, -S-, -N(Q)-, and -CO-. For example, -CO-O-divalent hydrocarbon group -O-, -CO-NH-divalent hydrocarbon group -O-, -O-divalent hydrocarbon group-, -(O-divalent hydrocarbon group) p Examples of such groups include -O- (p is an integer of 1 or more), a divalent hydrocarbon group -O-CO-, and a -CO-NH-divalent hydrocarbon group -O-. Among these divalent linking groups, a divalent linking group formed by combining at least two or more groups selected from the group consisting of a linear alkylene group having 1 to 10 carbon atoms, which may have a substituent, a branched or cyclic alkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 12 carbon atoms, which may have a substituent, -O-, -CO-, and -N(Q)-, is preferred because it provides better liquid crystal alignment properties. Q represents a hydrogen atom or a substituent.
[0025] Here, L A1 With respect to the divalent linking group represented by one embodiment of the formula (I), examples of the substituent which the above-mentioned hydrocarbon group and heterocyclic group may have, and the substituent represented by Q include a halogen atom, an alkyl group, an alkoxy group, an aryl group, an aryloxy group, a cyano group, a carboxy group, an alkoxycarbonyl group, and a hydroxyl group.
[0026] In the above formula (A), R A2 , R A3 , R A4 , R A5 and R A6 Each independently represents a hydrogen atom or a substituent. The type of the substituent is not particularly limited, and examples thereof include known substituents. A1 Examples of the substituent include those exemplified in one embodiment of the above. R A2 , R A3 , R A4 , R A5 and R A6 Among these, two adjacent groups may be bonded to form a ring.
[0027] R A2 , R A3 , R A4 , R A5 and R A6 The substituents represented by the formula (4) are preferably, each independently, a halogen atom, a linear alkyl group having 1 to 20 carbon atoms, a branched or cyclic alkyl group having 3 to 20 carbon atoms, a linear halogenated alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an aryloxy group having 6 to 20 carbon atoms, a hydroxy group, a cyano group, an amino group, or a group represented by the formula (4) below, because they provide better liquid crystal alignment. na - or -O-(CH2) na It may contain a linking group represented by -. na represents an integer of 1 to 10.
[0028] [ka]
[0029] In the above formula (4), * represents a bonding position. R A7 represents an alkyl group having 1 to 20 carbon atoms.
[0030] Examples of halogen atoms include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom, with a fluorine atom or a chlorine atom being preferred.
[0031] As the linear alkyl group, an alkyl group having 1 to 6 carbon atoms is preferable, and examples thereof include a methyl group, an ethyl group, and an n-propyl group. As the branched alkyl group, an alkyl group having 3 to 6 carbon atoms is preferable, and examples thereof include an isopropyl group and a tert-butyl group. The cyclic alkyl group is preferably an alkyl group having 3 to 6 carbon atoms, and examples thereof include a cyclopropyl group, a cyclopentyl group, and a cyclohexyl group.
[0032] As the linear halogenated alkyl group having 1 to 20 carbon atoms, a fluoroalkyl group having 1 to 12 carbon atoms is preferred, such as a trifluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a 2,2,3,3,4,4,5,5-octafluoropentyl group, and a 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl group. Among them, a 2,2,3,3,4,4,5,5-octafluoropentyl group or a 2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptyl group is preferred, because the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion is improved, and the adhesion between the first optically anisotropic layer and the second optically anisotropic layer is improved.
[0033] The alkoxy group having 1 to 20 carbon atoms is preferably an alkoxy group having 1 to 18 carbon atoms, more preferably an alkoxy group having 3 to 18 carbon atoms, and even more preferably an alkoxy group having 6 to 18 carbon atoms. Examples include a methoxy group, an ethoxy group, an n-butoxy group, a methoxyethoxy group, an n-hexyloxy group, an n-octyloxy group, an n-decyloxy group, an n-dodecyloxy group, and an n-tetradecyloxy group.
[0034] As the aryl group having 6 to 20 carbon atoms, an aryl group having 6 to 12 carbon atoms is preferable, and examples thereof include a phenyl group, an α-methylphenyl group, and a naphthyl group.
[0035] As the aryloxy group having 6 to 20 carbon atoms, an aryloxy group having 6 to 12 carbon atoms is preferable, and examples thereof include a phenyloxy group and a 2-naphthyloxy group.
[0036] Examples of the amino group include a primary amino group (-NH2); secondary amino groups such as a methylamino group; and tertiary amino groups such as a dimethylamino group, a diethylamino group, a dibenzylamino group, and a group having a nitrogen atom of a nitrogen-containing heterocyclic compound (e.g., pyrrolidine, piperidine, piperazine, etc.) as a bond.
[0037] The photoalignable group is easily interacted with the liquid crystal compound, and the liquid crystal alignment is improved. For this reason, R A2 , R A3 , R A4 , R A5 and R A6 Of these, at least R A4 represents the above-mentioned substituent (preferably an alkoxy group or a halogenated alkyl group having 1 to 20 carbon atoms), and further, for the reasons that the linearity of the obtained photoalignment polymer is improved, the interaction with the liquid crystal compound becomes easy, and the liquid crystal alignment property becomes better, R A2 , R A3 , R A5 and R A6 More preferably, each of represents a hydrogen atom.
[0038] Specific examples of the repeating unit A containing a photoalignment group include repeating units represented by the following formulae A-1 to A-30. The repeating unit represented by the following formula A-30 corresponds to a repeating unit containing a fluorine atom as well as a photoalignment group.
[0039] [ka] JPEG0007655931000006.jpg38147JPEG0007655931000007.jpg43147JPEG0007655931 000008.jpg44137JPEG0007655931000009.jpg44100JPEG0007655931000010.jpg45122
[0040] The content of the repeating unit A is preferably from 5 to 50% by mass, and more preferably from 10 to 40% by mass, based on the total repeating units of the photoalignable polymer, because this provides better liquid crystal alignment properties.
[0041] As described above, the photoalignable polymer of the present invention is a photoalignable polymer having a fluorine atom or a silicon atom, and is preferably a photoalignable polymer having a fluorine atom. Here, the positions and numbers of fluorine atoms and silicon atoms in the photo-aligned polymer are not particularly limited, but the fluorine atoms are preferably included in the side chain structure of the photo-aligned polymer. Also, the silicon atoms are preferably included in the main chain or side chain structure of the photo-aligned polymer, and more preferably included as a siloxane skeleton in the main chain or side chain structure.
[0042] The photoaligned polymer of the present invention preferably has a partial structure represented by the following formula (1), and more preferably has a group represented by the following formula (2), for the reason that the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion is improved. *-(CF2) m -* ···(1) *-(CF2) m -X (2)
[0043] In the above formulas (1) and (2), * represents a bonding position. In the above formulas (1) and (2), m represents an integer of 2 to 20, preferably an integer of 3 to 12, and more preferably an integer of 4 to 8. In the above formula (2), X represents a hydrogen atom or a fluorine atom, and is preferably a hydrogen atom because this improves the adhesion between the first optically anisotropic layer and the second optically anisotropic layer.
[0044] The photoalignable polymer of the present invention preferably has a group represented by the following formula (3) because the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion is improved. *-C(Y)(CF3)2···(3) In the above formula (3), * represents a bonding position, and Y represents a hydrogen atom or a substituent. Furthermore, examples of the substituent represented by one embodiment of Y in the above (3) include a halogen atom, an alkyl group, a halogenated alkyl group, an alkoxy group, an aryl group, an aryloxy group, a cyano group, a carboxy group, an alkoxycarbonyl group, and a hydroxyl group. In addition, Y in the above (3) is preferably a halogenated alkyl group, and more preferably a trifluoromethyl group (CF3 group), because this improves the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion.
[0045] In the present invention, the partial structure represented by the above formula (1) or the group represented by the above formula (2) or (3) may be included in the above repeating unit A, or may be included in a repeating unit other than the above repeating unit A. Here, the former embodiment is specifically exemplified by R A2 , R A3 , R A4 , R A5 and R A6 An example of the substituent represented by one embodiment of the formula (A) is an embodiment having a linear halogenated alkyl group having 2 to 20 carbon atoms. More specifically, for example, R A2 , R A3 , R A5 and R A6 represents a hydrogen atom, and R in the above formula (A) A4 represents a linear halogenated alkyl group having 2 to 20 carbon atoms. Examples of the linear halogenated alkyl group having 2 to 20 carbon atoms include the above-mentioned examples of the linear halogenated alkyl group having 1 to 20 carbon atoms excluding a trifluoromethyl group. On the other hand, the latter embodiment is preferably, specifically, for example, a copolymer having the above-mentioned repeating unit A and the below-mentioned repeating unit B containing a fluoroalkyl group.
[0046] The structure of the main chain of the repeating unit B containing a fluoroalkyl group is not particularly limited, and may be any known structure. For example, a skeleton selected from the group consisting of (meth)acrylic, styrene, siloxane, cycloolefin, methylpentene, amide, and aromatic ester is preferred. Among these, a skeleton selected from the group consisting of a (meth)acrylic, a siloxane, and a cycloolefin skeleton is more preferred, and a (meth)acrylic skeleton is even more preferred.
[0047] Examples of the repeating unit B containing a fluoroalkyl group include repeating units represented by the following formula (B-1) or (B-2). [ka]
[0048] In the above formulas (B-1) and (B-2), R B1 and R B2 represents a hydrogen atom or a substituent. In addition, in the above formulas (B-1) and (B-2), L B1 and L B2 represents a single bond or a divalent linking group. In the above formula (B-1), X represents a hydrogen atom or a fluorine atom, and m represents an integer of 2 to 20. In addition, in the above formula (B-2), Y represents a hydrogen atom or a substituent.
[0049] In the above formulas (B-1) and (B-2), R B1 and R B2 represents a hydrogen atom or a substituent. R B1 and R B2 The type of the substituent represented by one embodiment of the formula (A) is not particularly limited, and includes known substituents. A1 Among them, an alkyl group having 1 to 12 carbon atoms is preferable, a linear alkyl group having 1 to 8 carbon atoms or a branched alkyl group having 3 to 8 carbon atoms is more preferable, and a methyl group is even more preferable. Also, R B1 As a substituent represented by one embodiment of the formula (I), -L B1 -(CF2) m R may be a group represented by -X; B2 As a substituent represented by one embodiment of the formula (I), -L B2It may be a group represented by -C(CF3)2-Y. B1 , m and X, and L B2 and Y are the same as those defined in formulas (B-1) and (B-2) above. Also, R B1 and R B2 It is preferable that R represents a hydrogen atom or a methyl group.
[0050] In the above formulas (B-1) and (B-2), L B1 and L B2 represents a single bond or a divalent linking group. L B1 and L B2 Examples of the divalent linking group represented by one embodiment of the formula (A) include L A1 Examples of the divalent linking group include the same as those exemplified as the divalent linking group represented by one embodiment of the above. Among them, L B1 and L B2 The divalent linking group represented by one embodiment of the above is preferably a divalent linking group formed by combining at least two or more groups selected from the group consisting of a linear alkylene group having 1 to 10 carbon atoms which may have a substituent (preferably a fluorine atom), a branched or cyclic alkylene group having 3 to 10 carbon atoms, an arylene group having 6 to 12 carbon atoms which may have a substituent, -O-, -CO-, and -N(Q)-, for the reason that the liquid crystal alignment property is better. Q represents a hydrogen atom or a substituent. The definitions of the above groups are as follows: A1 The definitions of the divalent linking groups are the same as those of the divalent linking groups represented by one embodiment of the above.
[0051] In the above formula (B-1), X represents a hydrogen atom or a fluorine atom, and is preferably a hydrogen atom because this improves the adhesion between the first optically anisotropic layer and the second optically anisotropic layer.
[0052] In the above formula (B-1), m represents an integer of 2 to 20, preferably an integer of 3 to 12, and more preferably an integer of 4 to 8.
[0053] In the above formula (B-2), Y represents a hydrogen atom or a substituent. Here, examples of the substituent represented by one embodiment of Y in (B-2) above include those described in formula (3) above, and among them, a halogenated alkyl group is preferable, and a trifluoromethyl group (CF3 group) is more preferable, because the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion is improved.
[0054] Specific examples of the repeating unit B containing a fluoroalkyl group include repeating units represented by the following formulae B-1 to B-10.
[0055] [ka] JPEG0007655931000013.jpg37110JPEG0007655931000014.jpg4986
[0056] The content of repeating unit B in the photoalignable polymer of the present invention is not particularly limited, and is preferably 5 to 70 mass %, more preferably 10 to 60 mass %, of the total repeating units of the photoalignable polymer, because this allows for both good liquid crystal alignment properties and reduced unevenness in the film thickness of the second optically anisotropic layer.
[0057] The photoalignable polymer of the present invention is preferably a copolymer having a repeating unit C containing a crosslinkable group, because the liquid crystal alignment is improved by the effect of suppressing alignment relaxation due to the improvement in solvent resistance. The type of crosslinkable group is not particularly limited, and examples thereof include known crosslinkable groups. Among them, a cationic polymerizable group or a radical polymerizable group is preferred in terms of excellent adhesion to an upper layer disposed on the binder layer.
[0058] Examples of the cationically polymerizable group include an epoxy group, an epoxycyclohexyl group, and an oxetanyl group.
[0059] Examples of the radically polymerizable group include an acryloyl group, a methacryloyl group, a vinyl group, a styryl group, and an allyl group.
[0060] The structure of the main chain of the repeating unit C containing a crosslinkable group is not particularly limited, and may be any known structure. For example, a skeleton selected from the group consisting of (meth)acrylic, styrene, siloxane, cycloolefin, methylpentene, amide, and aromatic ester is preferred. Among these, a skeleton selected from the group consisting of a (meth)acrylic, a siloxane, and a cycloolefin skeleton is more preferred, and a (meth)acrylic skeleton is even more preferred.
[0061] Specific examples of the repeating unit C containing a crosslinkable group include repeating units represented by the following formulae C-1 to C-8.
[0062] [ka]
[0063] The content of the optional repeating unit C in the photoalignment polymer of the present invention is not particularly limited, but is preferably 10 to 90 mass %, more preferably 20 to 80 mass %, based on the total repeating units of the photoalignment polymer, because this improves the liquid crystal alignment property.
[0064] The photoalignable polymer of the present invention may have repeating units other than those mentioned above. Examples of monomers (radical polymerizable monomers) that form other repeating units than those described above include acrylic acid ester compounds, methacrylic acid ester compounds, maleimide compounds, acrylamide compounds, acrylonitrile, maleic anhydride, styrene compounds, and vinyl compounds.
[0065] The method for synthesizing the photoaligned polymer of the present invention is not particularly limited, and the polymer can be synthesized, for example, by mixing a monomer forming the repeating unit A described above, a monomer forming the repeating unit B described above, a monomer forming any repeating unit C described above, and a monomer forming any other repeating unit, and polymerizing the mixture in an organic solvent using a radical polymerization initiator.
[0066] The weight average molecular weight (Mw) of the photoalignable polymer of the present invention is not particularly limited, and is preferably from 10,000 to 500,000, more preferably from 10,000 to 300,000, and even more preferably from 30,000 to 150,000, because this improves the liquid crystal alignment property. The weight average molecular weight and number average molecular weight in the present invention are values measured by gel permeation chromatography (GPC) under the following conditions. Solvent (eluent): THF (tetrahydrofuran) ·Device name: TOSOH HLC-8320GPC Column: Three TOSOH TSKgel Super HZM-H (4.6mm x 15cm) columns connected together Column temperature: 40℃ Sample concentration: 0.1% by mass ·Flow rate: 1.0ml / min Calibration curve: TOSOH TSK standard polystyrene Calibration curve using 7 samples with Mw = 2,800,000 to 1,050 (Mw / Mn = 1.03 to 1.06)
[0067] <Liquid crystal composition> The second optically anisotropic layer having the photoalignable polymer of the present invention on the surface layer A is an optically anisotropic layer made of a liquid crystal layer. Therefore, the second optically anisotropic layer is preferably formed using, for example, a liquid crystal composition containing the above-mentioned photoalignable polymer and a liquid crystal compound (hereinafter also referred to as "composition for forming an optically anisotropic layer").
[0068] (liquid crystal compound) The liquid crystal compound contained in the composition for forming an optically anisotropic layer is a liquid crystal compound having a polymerizable group. Generally, liquid crystal compounds can be classified into rod-shaped and disc-shaped types based on their shape. Each type can be further divided into low molecular weight and high molecular weight types. High molecular weight generally refers to those with a degree of polymerization of 100 or more (Polymer Physics, Phase Transition Dynamics, Masao Doi, p. 2, Iwanami Shoten, 1992). In the present invention, any liquid crystal compound can be used, but it is preferable to use a rod-shaped liquid crystal compound or a discotic liquid crystal compound, and it is more preferable to use a rod-shaped liquid crystal compound.
[0069] In the present invention, a liquid crystal compound having a polymerizable group is used to fix the above-mentioned liquid crystal compound, and it is more preferable that the liquid crystal compound has two or more polymerizable groups in one molecule. In the case of a mixture of two or more liquid crystal compounds, it is preferable that at least one liquid crystal compound has two or more polymerizable groups in one molecule. After the liquid crystal compound is fixed by polymerization, it is no longer necessary for it to exhibit liquid crystallinity.
[0070] In addition, the type of polymerizable group is not particularly limited, and a functional group capable of addition polymerization reaction is preferable, and a polymerizable ethylenically unsaturated group or a ring-polymerizable group is preferable. More specifically, (meth)acryloyl group, vinyl group, styryl group, allyl group, etc. are preferable, and (meth)acryloyl group is more preferable. In addition, (meth)acryloyl group is a notation that means methacryloyl group or acryloyl group.
[0071] As the rod-shaped liquid crystal compound, for example, those described in claim 1 of JP-T-11-513019 and paragraphs
[0026] to
[0098] of JP-A-2005-289980 can be preferably used, and as the discotic liquid crystal compound, for example, those described in paragraphs
[0020] to
[0067] of JP-A-2007-108732 and paragraphs
[0013] to
[0108] of JP-A-2010-244038 can be preferably used, but are not limited to these.
[0072] In the present invention, for reasons of improving the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion and improving the light resistance of the optical laminate, it is preferred that at least one of the second optically anisotropic layer and the first optically anisotropic layer described below, particularly the optically anisotropic layer exhibiting reverse wavelength dispersion among the second optically anisotropic layer and the first optically anisotropic layer described below, is an optically anisotropic layer in which the orientation of a liquid crystal compound having any one of aromatic rings selected from the group consisting of groups represented by the following formulae (Ar-1) to (Ar-7) is fixed. Therefore, the liquid crystal compound contained in the liquid crystal composition forming the second optically anisotropic layer and the first optically anisotropic layer described below that exhibits reverse wavelength dispersion is preferably a liquid crystal compound having any aromatic ring selected from the group consisting of groups represented by the following formulas (Ar-1) to (Ar-7). [ka]
[0073] In the above formulae (Ar-1) to (Ar-7), * represents a bonding position, that is, a bonding position to a portion contained in the liquid crystal compound other than the above aromatic ring.
[0074] In addition, in the above formula (Ar-1), Q 1 represents N or CH, and Q 2 is -S-, -O-, or -N(R 6 )-, and R 6 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; Y 1 represents an aromatic hydrocarbon group having 6 to 12 carbon atoms which may have a substituent, an aromatic heterocyclic group having 3 to 12 carbon atoms which may have a substituent, or an alicyclic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent, and one or more of -CH2- constituting the alicyclic hydrocarbon group may be substituted with -O-, -S- or -NH-.
[0075] Here, R 6Specific examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, and an n-hexyl group.
[0076] Also, Y 1 Examples of the aromatic hydrocarbon group having 6 to 12 carbon atoms include aryl groups such as a phenyl group, a 2,6-diethylphenyl group, and a naphthyl group. Y 1 Examples of the aromatic heterocyclic group having 3 to 12 carbon atoms include heteroaryl groups such as a thienyl group, a thiazolyl group, a furyl group, and a pyridyl group. Y 1 Examples of the alicyclic hydrocarbon group having 6 to 20 carbon atoms include a cyclohexylene group, a cyclopentylene group, a norbornylene group, and an adamantylene group.
[0077] Y 1 Examples of the substituent that may be possessed by the compound include an alkyl group, an alkoxy group, an alkylcarbonyl group, an alkoxycarbonyl group, an alkylcarbonyloxy group, an alkylamino group, a dialkylamino group, an alkylamide group, an alkenyl group, an alkynyl group, a halogen atom, a cyano group, a nitro group, an alkylthiol group, and an N-alkylcarbamate group. Among these, an alkyl group, an alkoxy group, an alkoxycarbonyl group, an alkylcarbonyloxy group, or a halogen atom is preferable. The alkyl group is preferably a linear, branched or cyclic alkyl group having 1 to 18 carbon atoms, more preferably an alkyl group having 1 to 8 carbon atoms (e.g., a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a t-butyl group, a cyclohexyl group, etc.), still more preferably an alkyl group having 1 to 4 carbon atoms, and particularly preferably a methyl group or an ethyl group. The alkoxy group is preferably an alkoxy group having 1 to 18 carbon atoms, more preferably an alkoxy group having 1 to 8 carbon atoms (for example, a methoxy group, an ethoxy group, an n-butoxy group, a methoxyethoxy group, etc.), still more preferably an alkoxy group having 1 to 4 carbon atoms, and particularly preferably a methoxy group or an ethoxy group. Examples of the alkoxycarbonyl group include groups in which an oxycarbonyl group (-O-CO- group) is bonded to the alkyl group exemplified above. Among these, a methoxycarbonyl group, an ethoxycarbonyl group, an n-propoxycarbonyl group or an isopropoxycarbonyl group is preferred, and a methoxycarbonyl group is more preferred. Examples of the alkylcarbonyloxy group include groups in which a carbonyloxy group (-CO-O- group) is bonded to the alkyl group exemplified above. Among these, a methylcarbonyloxy group, an ethylcarbonyloxy group, an n-propylcarbonyloxy group, or an isopropylcarbonyloxy group is preferable, and a methylcarbonyloxy group is more preferable. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom, and among these, a fluorine atom or a chlorine atom is preferable.
[0078] In addition, in the above formulas (Ar-1) to (Ar-7), Z 1 , Z 2 and Z 3 each independently represents a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, a monovalent alicyclic hydrocarbon group having 3 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a monovalent aromatic heterocyclic group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -OR 7 , -NR 8 R 9 , -SR 10 , -COOR 11 , or -COR 12 R 7 ~R 12 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; Z 1 and Z 2 may be bonded to each other to form an aromatic ring.
[0079] Here, the monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms is preferably an alkyl group having 1 to 15 carbon atoms, more preferably an alkyl group having 1 to 8 carbon atoms, specifically, a methyl group, an ethyl group, an isopropyl group, a tert-pentyl group (1,1-dimethylpropyl group), a tert-butyl group, or a 1,1-dimethyl-3,3-dimethyl-butyl group is further preferable, and a methyl group, an ethyl group, or a tert-butyl group is particularly preferable. Examples of the monovalent alicyclic hydrocarbon group having 3 to 20 carbon atoms include monocyclic saturated hydrocarbon groups such as a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclodecyl group, a methylcyclohexyl group, and an ethylcyclohexyl group; monocyclic unsaturated hydrocarbon groups such as a cyclobutenyl group, a cyclopentenyl group, a cyclohexenyl group, a cycloheptenyl group, a cyclooctenyl group, a cyclodecenyl group, a cyclopentadienyl group, a cyclohexadienyl group, a cyclooctadienyl group, and a cyclodecadiene group; bicyclo[2.2.1]heptyl group, bicyclo[2.2.2]octyl group, tricyclo[5.2.1.0]heptyl group, bicyclo[2.2.2]octyl group, tricyclo[5.2.1.0]heptyl group, tricyclo[5.2.1.0]octyl group, tricyclo[5.2.1.0]hex ... 2,6 ]decyl group, tricyclo[3.3.1.1 3,7 ]decyl group, tetracyclo[6.2.1.1 3,6 .0 2,7 ]dodecyl group, adamantyl group and other polycyclic saturated hydrocarbon groups; and the like. Specific examples of the monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms include a phenyl group, a 2,6-diethylphenyl group, a naphthyl group, and a biphenyl group, with an aryl group having 6 to 12 carbon atoms (particularly a phenyl group) being preferred. Specific examples of the monovalent aromatic heterocyclic group having 6 to 20 carbon atoms include a 4-pyridyl group, a 2-furyl group, a 2-thienyl group, a 2-pyrimidinyl group, and a 2-benzothiazolyl group. Examples of halogen atoms include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, and among these, a fluorine atom, a chlorine atom, and a bromine atom are preferred. On the other hand, R 7 ~R 10Specific examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, and an n-hexyl group.
[0080] Also, Z 1 and Z 2 As described above, may be bonded to each other to form an aromatic ring. For example, Z 1 and Z 2 Examples of the structure in which Q are bonded to each other to form an aromatic ring include a group represented by the following formula (Ar-1a). In the following formula (Ar-1a), * represents a bonding position, and Q 1 , Q 2 and Y 1 Examples of the alkyl group include those explained in relation to the above formula (Ar-1). [ka]
[0081] In addition, in the above formulas (Ar-2) and (Ar-3), A 3 and A 4 are each independently -O-, -N(R 13 R represents a group selected from the group consisting of -, -S-, and -CO-; 13 represents a hydrogen atom or a substituent. R 13 The substituent represented by the formula (Ar-1) is preferably Y 1 The substituents may be the same as those which may be possessed by the group.
[0082] In the above formula (Ar-2), X represents a hydrogen atom or a nonmetallic atom of Groups 14 to 16 which may have a substituent bonded thereto. Examples of the nonmetallic atom of Groups 14 to 16 represented by X include an oxygen atom, a sulfur atom, a hydrogen atom, or a nitrogen atom bonded to a substituent [=NR N1 ,R N1 represents a hydrogen atom or a substituent. ], a carbon atom to which a hydrogen atom or a substituent is bonded [=C-(RC1 )2,R C1 represents a hydrogen atom or a substituent. Specific examples of the substituent include an alkyl group, an alkoxy group, an alkyl-substituted alkoxy group, a cyclic alkyl group, an aryl group (e.g., a phenyl group, a naphthyl group, etc.), a cyano group, an amino group, a nitro group, an alkylcarbonyl group, a sulfo group, and a hydroxyl group.
[0083] In addition, in the above formula (Ar-3), D 7 and D. 8 each independently represents a single bond, -CO-, -O-, -S-, -C(=S)-, or -CR 1 R 2 -, -CR 3 =CR 4 -, -NR 5 -, or a divalent linking group consisting of two or more of these, R 1 ~R 5 each independently represents a hydrogen atom, a fluorine atom, or an alkyl group having 1 to 12 carbon atoms.
[0084] Here, D 7 and D. 8 Examples of the divalent linking group in one embodiment of the formula (1) include -CO-, -O-, -CO-O-, -C(=S)O-, -CR 1 R 2 -, -CR 1 R 2 -CR 1 R 2 -, -O-CR 1 R 2 -, -CR 1 R 2 -O-CR 1 R 2 -,-CO-O-CR 1 R 2 -, -O-CO-CR 1 R 2 -, -CR 1 R 2 -O-CO-CR 1 R 2 -, -CR 1 R 2 -CO-O-CR 1 R2 -, -NR 5 -CR 1 R 2 - and -CO-NR 5 - and others. R 1 , R 2 and R 5 each independently represents a hydrogen atom, a fluorine atom, or an alkyl group having 1 to 12 carbon atoms. Among these, any one of -CO-, -O- and -CO-O- is preferable.
[0085] In addition, in the above formula (Ar-3), SP 3 and S.P. 4 each independently represents a single bond, a linear or branched alkylene group having 1 to 12 carbon atoms, or a divalent linking group in which one or more of -CH2- constituting a linear or branched alkylene group having 1 to 12 carbon atoms is replaced with -O-, -S-, -NH-, -N(Q)-, or -CO-, and Q represents a substituent. 1 The substituents include the same ones as those which may be possessed by the group.
[0086] Here, SP 3 and S.P. 4 Suitable examples of the linear or branched alkylene group having 1 to 12 carbon atoms in one embodiment of the formula (1) include a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, a methylhexylene group, and a heptylene group. 1 and S.P. 2 As described above, may be a divalent linking group in which one or more of -CH2- constituting a linear or branched alkylene group having 1 to 12 carbon atoms are replaced with -O-, -S-, -NH-, -N(Q)-, or -CO-, and examples of the substituent represented by Q include Y in the above formula (Ar-1). 1 The substituents include the same ones as those which may be possessed by the group.
[0087] In addition, in the above formula (Ar-3), L 3 and L 4each independently represents a monovalent organic group. L 3 and L 4 Examples of the monovalent organic group represented by the formula (I) include an alkyl group, an aryl group, and a heteroaryl group. The alkyl group may be linear, branched or cyclic, but is preferably linear. The alkyl group preferably has 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms, and even more preferably 1 to 10 carbon atoms. The aryl group may be either monocyclic or polycyclic, but is preferably monocyclic. The aryl group preferably has 6 to 25 carbon atoms, and more preferably has 6 to 10 carbon atoms. The heteroaryl group may be a monocyclic or polycyclic ring. The number of heteroatoms constituting the heteroaryl group is preferably 1 to 3. The heteroatoms constituting the heteroaryl group are preferably a nitrogen atom, a sulfur atom, or an oxygen atom. The number of carbon atoms in the heteroaryl group is preferably 6 to 18, and more preferably 6 to 12. The alkyl group, aryl group and heteroaryl group may be unsubstituted or may have a substituent. Examples of the substituent include Y in the above formula (Ar-1). 1 The substituents may be the same as those which may be possessed by the group.
[0088] In addition, in the above formulas (Ar-4) to (Ar-7), Ax represents an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocycles. In the above formulas (Ar-4) to (Ar-7), Ay represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms which may have a substituent, or an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocycles. Here, the aromatic rings in Ax and Ay may have a substituent, and Ax and Ay may be bonded to form a ring. Also, Q 3 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may have a substituent. Examples of Ax and Ay include those described in paragraphs
[0039] to
[0095] of WO 2014 / 010325. Also, Q 3 Specific examples of the alkyl group having 1 to 20 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, and an n-hexyl group. 1 The substituents include the same ones as those which may be possessed by the group.
[0089] In the present invention, the liquid crystal compound is preferably a compound represented by the following formula (I) because it can be aligned at a relatively low temperature. In the following formula (I), Ar represents any aromatic ring selected from the group consisting of the groups represented by the above formulas (Ar-1) to (Ar-7). However, when q1 in the following formula (I) is 2, the multiple Ar may be the same or different. L 1 -SP 1 -D 5 -(A 1 ) a1 -D 3 -(G 1 ) g1 -D 1 -〔Ar-D 2 〕 q1 -(G 2 ) g2 -D 4 -(A 2 ) a2 -D 6 -SP 2 -L 2 (I)
[0090] In the above formula (I), a1, a2, g1, and g2 each independently represent 0 or 1, provided that at least one of a1 and g1 represents 1, and at least one of a2 and g2 represents 1. In the above formula (I), q1 represents 1 or 2. In addition, in the above formula (I), D 1 , D 2 , D3 , D 4 , D 5 and D. 6 each independently represents a single bond, -CO-, -O-, -S-, -C(=S)-, or -CR 1 R 2 -, -CR 3 =CR 4 -, -NR 5 -, or a divalent linking group consisting of two or more of these, R 1 ~R 5 each independently represents a hydrogen atom, a fluorine atom, or an alkyl group having 1 to 12 carbon atoms; provided that when q1 is 2, multiple D 2 may be the same or different. In addition, in the above formula (I), G 1 and G 2 each independently represents an aromatic ring having 6 to 20 carbon atoms which may have a substituent, or a divalent alicyclic hydrocarbon group having 5 to 20 carbon atoms which may have a substituent, and one or more of -CH2- constituting the alicyclic hydrocarbon group may be substituted with -O-, -S- or -NH-. In addition, in the above formula (I), A 1 and A 2 each independently represents an aromatic ring having 6 to 20 carbon atoms which may have a substituent, or a divalent alicyclic hydrocarbon group having 5 to 20 carbon atoms which may have a substituent, and one or more of -CH2- constituting the alicyclic hydrocarbon group may be substituted with -O-, -S- or -NH-. In addition, in the above formula (I), SP 1 and S.P. 2 each independently represents a single bond, a linear or branched alkylene group having 1 to 12 carbon atoms, or a divalent linking group in which one or more -CH2- constituting the linear or branched alkylene group having 1 to 12 carbon atoms is substituted with -O-, -S-, -NH-, -N(Q)-, or -CO-, and Q represents a substituent. In addition, in the above formula (I), L 1 and L 2 each independently represents a monovalent organic group; L 1 and L 2At least one of the groups represents a polymerizable group. However, when Ar is an aromatic ring represented by the above formula (Ar-3), L 1 and L 2 And L in the above formula (Ar-3) 3 and L 4 At least one of these represents a polymerizable group.
[0091] In the above formula (I), it is preferable that a1, a2, g1 and g2 are all 1.
[0092] In the above formula (I), q1 is preferably 1.
[0093] In the above formula (I), D 1 , D 2 , D 3 , D 4 , D 5 and D. 6 As a divalent linking group in one embodiment of the present invention, there is a divalent linking group represented by the formula (Ar-3) 7 and D. 8 Examples of the above-mentioned examples are the same as those described above. Among these, any one of -CO-, -O- and -CO-O- is preferable.
[0094] In the above formula (I), G 1 and G 2 Examples of the aromatic ring having 6 to 20 carbon atoms in one embodiment include aromatic hydrocarbon rings such as a benzene ring, a naphthalene ring, an anthracene ring, and a phenanthroline ring; and aromatic heterocycles such as a furan ring, a pyrrole ring, a thiophene ring, a pyridine ring, a thiazole ring, and a benzothiazole ring; and among these, a benzene ring (for example, a 1,4-phenyl group, etc.) is preferable.
[0095] In the above formula (I), G 1 and G 2 The divalent alicyclic hydrocarbon group having 5 to 20 carbon atoms shown in one embodiment of is preferably a 5-membered or 6-membered ring. The alicyclic hydrocarbon group may be saturated or unsaturated, but is preferably a saturated alicyclic hydrocarbon group. 1 and G 2For the divalent alicyclic hydrocarbon group represented by the following formula (I), reference can be made to the description in paragraph
[0078] of JP2012-21068A, the contents of which are incorporated herein by reference.
[0096] In the present invention, G in the above formula (I) 1 and G 2 is preferably a cycloalkane ring. Specific examples of the cycloalkane ring include a cyclohexane ring, a cycloheptane ring, a cyclooctane ring, a cyclododecane ring, and a cyclodocosane ring. Of these, a cyclohexane ring is preferred, a 1,4-cyclohexylene group is more preferred, and a trans-1,4-cyclohexylene group is even more preferred.
[0097] In addition, in the above formula (I), G 1 and G 2 With respect to the above, examples of the substituent that the aromatic ring having 6 to 20 carbon atoms or the divalent alicyclic hydrocarbon group having 5 to 20 carbon atoms may have include Y 1 The substituents may be the same as those which may be possessed by the group.
[0098] In the above formula (I), A 1 and A 2 As an aromatic ring having 6 to 20 carbon atoms in one embodiment, G in the above formula (I) 1 and G 2 Examples of the above-mentioned examples are the same as those described above. In addition, in the above formula (I), A 1 and A 2 As a divalent alicyclic hydrocarbon group having 5 to 20 carbon atoms, there is shown an embodiment of the above formula (I). 1 and G 2 Examples of the above-mentioned examples are the same as those described above. In addition, A 1 and A 2 With respect to the above, examples of the substituent that the aromatic ring having 6 to 20 carbon atoms or the divalent alicyclic hydrocarbon group having 5 to 20 carbon atoms may have include Y 1The substituents include the same ones as those which may be possessed by the group.
[0099] In the above formula (I), SP 1 and S.P. 2 As an example of the linear or branched alkylene group having 1 to 12 carbon atoms, there is shown the following formula (Ar-3): 3 and S.P. 4 Examples of the above-mentioned examples are the same as those described above.
[0100] In the above formula (I), L 1 and L 2 The monovalent organic group represented by the formula (Ar-3) is 3 and L 4 Examples of the above-mentioned examples are the same as those described above.
[0101] In the above formula (I), L 1 and L 2 The polymerizable group represented by at least one of the above is not particularly limited, but is preferably a polymerizable group capable of radical polymerization or cationic polymerization. As the radical polymerizable group, a known radical polymerizable group can be used, and a suitable one can be an acryloyloxy group or a methacryloyloxy group. In this case, it is known that the polymerization rate of the acryloyloxy group is generally fast, and from the viewpoint of improving productivity, the acryloyloxy group is preferred, but the methacryloyloxy group can also be used as the polymerizable group. As the cationic polymerizable group, a known cationic polymerizable group can be used, and specific examples thereof include an alicyclic ether group, a cyclic acetal group, a cyclic lactone group, a cyclic thioether group, a spiro orthoester group, and a vinyloxy group. Among them, an alicyclic ether group or a vinyloxy group is preferable, and an epoxy group, an oxetanyl group, or a vinyloxy group is particularly preferable. Particularly preferred examples of the polymerizable group include the polymerizable groups represented by any of the following formulas (P-1) to (P-20).
[0102] [ka]
[0103] In the above formula (I), L in the above formula (I) is preferably selected because it provides good durability. 1 and L 2 However, each of them is preferably a polymerizable group, and more preferably an acryloyloxy group or a methacryloyloxy group.
[0104] Examples of the compound represented by the above formula (I) include compounds represented by general formula (1) described in JP-A-2010-084032 (particularly, the compounds described in paragraphs
[0067] to
[0073] ), compounds represented by general formula (II) described in JP-A-2016-053709 (particularly, the compounds described in paragraphs
[0036] to
[0043] ), and compounds represented by general formula (1) described in JP-A-2016-081035 (particularly, the compounds described in paragraphs
[0043] to
[0055] ).
[0105] Suitable examples of the compound represented by formula (I) include compounds represented by the following formulas (1) to (22). Specifically, examples of the compound represented by formulas (1) to (22) include compounds having the side chain structures shown in Tables 1 to 3 below as K (side chain structure). In the following Tables 1 to 3, the "*" shown in the side chain structure of K indicates the bonding position with the aromatic ring. In the side chain structures represented by 2-2 in Table 2 and 3-2 in Table 3, the groups adjacent to the acryloyloxy group and the methacryloyl group, respectively, represent a propylene group (a group in which a methyl group is substituted with an ethylene group), and represent a mixture of positional isomers in which the position of the methyl group is different. [ka] JPEG0007655931000020.jpg132136
[0106] [Table 1]
[0107] [Table 2]
[0108] [Table 3]
[0109] (Polymerization initiator) The composition for forming an optically anisotropic layer preferably contains a polymerization initiator. The polymerization initiator is not particularly limited, and examples thereof include a thermal polymerization initiator and a photopolymerization initiator depending on the type of polymerization reaction. The polymerization initiator is preferably a photopolymerization initiator capable of initiating a polymerization reaction by irradiation with ultraviolet light. Examples of the photopolymerization initiator include α-carbonyl compounds (described in U.S. Pat. Nos. 2,367,661 and 2,367,670), acyloin ethers (described in U.S. Pat. No. 2,448,828), α-hydrocarbon-substituted aromatic acyloin compounds (described in U.S. Pat. No. 2,722,512), polynuclear quinone compounds (described in U.S. Pat. Nos. 3,046,127 and 2,951,758), and combinations of triaryl imidazole dimers and p-aminophenyl ketones. Examples of such compounds include compounds (described in U.S. Pat. No. 3,549,367), acridine and phenazine compounds (described in JP-A-60-105667 and U.S. Pat. No. 4,239,850), oxadiazole compounds (described in U.S. Pat. No. 4,212,970), and acylphosphine oxide compounds (described in JP-B-63-040799, JP-B-5-029234, JP-A-10-095788, and JP-A-10-029997).
[0110] (Surfactant) The composition for forming an optically anisotropic layer preferably does not contain a surfactant in order to prevent repelling when applying a liquid crystal composition for forming a first optically anisotropic layer onto a second optically anisotropic layer. However, a surfactant may be used in combination within a range that allows the element ratio of fluorine or silicon on the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer to be adjusted to 0.05 to 15.00 atomic %. As the surfactant, it is preferable to use a surfactant with high elution properties. The highly elutable surfactant herein refers to a surfactant in which, when a solvent is applied to a cured film containing the surfactant, at least a part of the surfactant in the cured film is eluted into the applied solvent. Preferred specific examples of such surfactants include surfactants that have a fluorine atom or a silicon atom and have a weight average molecular weight of 10,000 or less. If such a surfactant has high elution properties, the surfactant will be easily extracted into the solvent used to form the upper layer (first optically anisotropic layer), which is thought to result in good interaction between the photoalignable groups of the photoalignable polymer in the lower layer (second optically anisotropic layer) and the liquid crystal compound in the upper layer, resulting in good liquid crystal alignment.
[0111] (solvent) The composition for forming an optically anisotropic layer preferably contains a solvent from the viewpoint of workability. Examples of the solvent include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone), ethers (e.g., dioxane and tetrahydrofuran), aliphatic hydrocarbons (e.g., hexane), alicyclic hydrocarbons (e.g., cyclohexane), aromatic hydrocarbons (e.g., toluene, xylene, and trimethylbenzene), halogenated carbons (e.g., dichloromethane, dichloroethane, dichlorobenzene, and chlorotoluene), esters (e.g., methyl acetate, ethyl acetate, and butyl acetate), water, alcohols (e.g., ethanol, isopropanol, butanol, and cyclohexanol), cellosolves (e.g., methyl cellosolve and ethyl cellosolve), cellosolve acetates, sulfoxides (e.g., dimethyl sulfoxide), and amides (e.g., dimethylformamide and dimethylacetamide). The solvent may be used alone or in combination of two or more kinds.
[0112] The second optically anisotropic layer of the optical laminate of the present invention is preferably formed using the above-mentioned composition for forming an optically anisotropic layer, and the surface of the second optically anisotropic layer is preferably a layer having an alignment control ability. More specifically, the second optically anisotropic layer can be prepared, for example, by a manufacturing method including a coating step of coating the above-mentioned optically anisotropic layer-forming composition of the present invention onto the surface of a support, and a light irradiation step of irradiating the coating film of the optically anisotropic layer-forming composition with polarized light or unpolarized light from an oblique direction to the coating film surface.
[0113] <Coating process> The support used in the coating step includes, for example, a glass substrate and a polymer film. Examples of materials for polymer films include cellulose-based polymers; acrylic-based polymers having acrylic ester polymers such as polymethyl methacrylate and lactone ring-containing polymers; thermoplastic norbornene-based polymers; polycarbonate-based polymers; polyester-based polymers such as polyethylene terephthalate and polyethylene naphthalate; styrene-based polymers such as polystyrene and acrylonitrile-styrene copolymers; polyolefin-based polymers such as polyethylene, polypropylene, and ethylene-propylene copolymers; vinyl chloride-based polymers; amide-based polymers such as nylon and aromatic polyamides; imide-based polymers; sulfone-based polymers; polyethersulfone-based polymers; polyetheretherketone-based polymers; polyphenylene sulfide-based polymers; vinylidene chloride-based polymers; vinyl alcohol-based polymers; vinyl butyral-based polymers; arylate-based polymers; polyoxymethylene-based polymers; epoxy-based polymers; or mixtures of these polymers. An alignment layer may be disposed on the support.
[0114] The thickness of the support is not particularly limited, and is preferably from 5 to 200 μm, more preferably from 10 to 100 μm, and further preferably from 20 to 90 μm.
[0115] The coating method in the coating step is not particularly limited and can be appropriately selected depending on the purpose. Examples of the coating method include spin coating, die coating, gravure coating, flexographic printing, and inkjet printing.
[0116] <Light irradiation process> In the light irradiation step, the polarized light to be irradiated onto the coating film of the composition for forming an optically anisotropic layer is not particularly limited. Examples include linearly polarized light, circularly polarized light, and elliptically polarized light, and among these, linearly polarized light is preferred. Furthermore, the "oblique direction" in which the unpolarized light is irradiated is not particularly limited as long as it is a direction inclined at a polar angle θ (0<θ<90°) with respect to the normal direction to the coating surface, and can be appropriately selected depending on the purpose, but it is preferable that θ is 20 to 80°.
[0117] The wavelength of the polarized or unpolarized light is not particularly limited as long as it can impart alignment control ability to liquid crystal molecules to a coating film of the composition for forming an optically anisotropic layer, and examples thereof include ultraviolet light, near ultraviolet light, visible light, etc. Among them, near ultraviolet light of 250 nm to 450 nm is particularly preferred. Examples of light sources for irradiating polarized or non-polarized light include xenon lamps, high-pressure mercury lamps, extra-high-pressure mercury lamps, and metal halide lamps. By using an interference filter or a color filter for the ultraviolet light or visible light obtained from such light sources, the wavelength range of the light to be irradiated can be limited. By using a polarizing filter or a polarizing prism for the light from such light sources, linearly polarized light can be obtained.
[0118] The integrated amount of polarized or unpolarized light is not particularly limited as long as it can impart alignment control ability to liquid crystal molecules to a coating film of the composition for forming an optically anisotropic layer. It is not particularly limited, but is preferably 1 to 300 mJ / cm. 2 is preferable, and 5 to 100 mJ / cm 2 is more preferred. The illuminance of the polarized or unpolarized light is not particularly limited as long as it can impart an alignment control ability to liquid crystal molecules to the coating film of the composition for forming an optically anisotropic layer, but is preferably 0.1 to 300 mW / cm. 2 is preferable, and 1 to 100 mW / cm 2 is more preferred.
[0119] The thickness of the second optically anisotropic layer is not particularly limited, and is preferably 0.1 to 10 μm, more preferably 0.2 to 5 μm, and even more preferably 0.3 to 2 μm, because this improves the liquid crystal alignment property of the first optically anisotropic layer.
[0120] [First Optically Anisotropic Layer] The first optically anisotropic layer of the optical laminate of the present invention is laminated directly on the above-mentioned second optically anisotropic layer, and is an optically anisotropic layer made of a liquid crystal layer. The first optically anisotropic layer is preferably formed using a liquid crystal composition containing a liquid crystal compound. Here, examples of the liquid crystal composition for forming the first optically anisotropic layer include compositions containing the liquid crystal compound, polymerization initiator, and solvent described above in the composition for forming the optically anisotropic layer.
[0121] The thickness of the first optically anisotropic layer is not particularly limited, and is preferably from 0.1 to 10 μm, and more preferably from 0.5 to 5 μm.
[0122] The thickness of the optical layered body of the present invention is not particularly limited, but is preferably from 0.2 to 10 μm, more preferably from 0.5 to 5 μm, and particularly preferably from 1 to 4 μm.
[0123] As described above, in the optical laminate of the present invention, the atomic ratio of fluorine or silicon on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer is 0.05 to 15.00 atomic %, but in terms of the balance between the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion and the adhesion between the first optically anisotropic layer and the second optically anisotropic layer, it is preferably 0.10 to 10.00 atomic %, and more preferably 0.20 to 8.00 atomic %.
[0124] In view of the usefulness of the optical laminate of the present invention in that it can be used as a circular polarizing plate or a compensation layer for a liquid crystal display device, the first optically anisotropic layer is preferably a positive A plate, and more preferably a positive A plate exhibiting reverse wavelength dispersion. In the optical laminate of the present invention, the second optically anisotropic layer is preferably a positive C plate, from the viewpoint of optical compensation in an oblique direction of the first optically anisotropic layer.
[0125] Here, the positive A plate and the positive C plate are defined as follows: When the refractive index in the slow axis direction (the direction in which the in-plane refractive index is maximum) in the film plane is nx, the refractive index in the direction perpendicular to the in-plane slow axis is ny, and the refractive index in the thickness direction is nz, the positive A plate satisfies the relationship in formula (A1), and the positive C plate satisfies the relationship in formula (C1). Note that the positive A plate has a positive Rth value, and the positive C plate has a negative Rth value. Formula (A1) nx>ny≒nz Formula (C1) nz>nx≒ny It should be noted that the above "≒" includes not only the case where the two are completely identical, but also the case where the two are substantially identical. "Substantially the same" means that, for example, in the case of a positive A plate, "ny≒nz" includes a case where (ny-nz)×d (where d is the thickness of the film) is -10 to 10 nm, preferably -5 to 5 nm, and "nx≒nz" includes a case where (nx-nz)×d is -10 to 10 nm, preferably -5 to 5 nm. Also, in the case of a positive C plate, "nx≒ny" includes a case where (nx-ny)×d (where d is the thickness of the film) is 0 to 10 nm, preferably 0 to 5 nm.
[0126] When the optically anisotropic layer is a positive A plate, from the viewpoint of functioning as a λ / 4 plate, Re(550) is preferably from 100 to 180 nm, more preferably from 120 to 160 nm, and further preferably from 130 to 150 nm. Here, the term "λ / 4 plate" refers to a plate having a λ / 4 function, specifically, a plate having the function of converting linearly polarized light of a certain wavelength into circularly polarized light (or circularly polarized light into linearly polarized light).
[0127] [Polarizing plate] The polarizing plate of the present invention comprises the above-mentioned optical laminate of the present invention and a polarizer. Furthermore, when the above-mentioned optical laminate of the present invention is a λ / 4 plate, the polarizing plate of the present invention can be used as a circular polarizing plate. When the polarizing plate of the present invention is used as a circular polarizing plate, the above-mentioned optical laminate of the present invention (particularly, the first optically anisotropic layer) is used as a λ / 4 plate (positive A plate), and the angle between the slow axis of the λ / 4 plate and the absorption axis of the polarizer described later is preferably 30 to 60°, more preferably 40 to 50°, even more preferably 42 to 48°, and particularly preferably 45°. Here, the "slow axis" of the λ / 4 plate or positive A plate means the direction in which the refractive index is maximum in the plane of the λ / 4 plate or positive A plate, and the "absorption axis" of the polarizer means the direction in which the absorbance is highest.
[0128] [Polarizer] The polarizer in the polarizing plate of the present invention is not particularly limited as long as it is a member having a function of converting light into a specific linearly polarized light, and a conventionally known absorptive polarizer and reflective polarizer can be used. Examples of absorption-type polarizers include iodine-based polarizers, dye-based polarizers using dichroic dyes, polyene-based polarizers, etc. Iodine-based polarizers and dye-based polarizers include coating-type polarizers and stretching-type polarizers, and either can be used, but polarizers made by adsorbing iodine or a dichroic dye to polyvinyl alcohol and stretching it are preferred. In addition, methods of obtaining a polarizer by stretching and dyeing a laminated film in which a polyvinyl alcohol layer is formed on a substrate can be described in Japanese Patent No. 5048120, Japanese Patent No. 5143918, Japanese Patent No. 4691205, Japanese Patent No. 4751481, and Japanese Patent No. 4751486. These known techniques related to polarizers can also be preferably used. As the reflective polarizer, a polarizer in which thin films with different birefringence are laminated, a wire grid type polarizer, a polarizer in which a cholesteric liquid crystal having a selective reflection region is combined with a quarter-wave plate, and the like are used. Among these, a polarizer containing a polyvinyl alcohol resin (a polymer containing -CH2-CHOH- as a repeating unit, in particular at least one selected from the group consisting of polyvinyl alcohol and an ethylene-vinyl alcohol copolymer) is preferred because of its superior adhesion.
[0129] In the present invention, the thickness of the polarizer is not particularly limited, but is preferably from 3 μm to 60 μm, more preferably from 3 μm to 30 μm, and even more preferably from 3 μm to 10 μm.
[0130] [Image display device] The image display device of the present invention is an image display device having the optical laminate of the present invention or the polarizing plate of the present invention. The display element used in the image display device of the present invention is not particularly limited, and examples thereof include a liquid crystal cell, an organic electroluminescence (hereinafter abbreviated as "EL") display panel, and a plasma display panel. Among these, a liquid crystal cell or an organic EL display panel is preferred, and a liquid crystal cell is more preferred. That is, the image display device of the present invention is preferably a liquid crystal display device using a liquid crystal cell as a display element, or an organic EL display device using an organic EL display panel as a display element.
[0131] The liquid crystal cell used in the liquid crystal display device is preferably in VA (Vertical Alignment) mode, OCB (Optically Compensated Bend) mode, IPS (In-Plane-Switching) mode, FFS (Fringe-Field-Switching) mode, or TN (Twisted Nematic) mode, but is not limited to these.
[0132] A preferred embodiment of the organic EL display device includes, from the viewing side, a polarizer, the optical laminate of the present invention, and an organic EL display panel in this order. An organic EL display panel is a member in which a light-emitting layer or a plurality of organic compound thin films including a light-emitting layer are formed between a pair of electrodes, an anode and a cathode, and may have a hole injection layer, a hole transport layer, an electron injection layer, an electron transport layer, a protective layer, etc. in addition to the light-emitting layer, and each of these layers may have other functions. Various materials can be used to form each layer. EXAMPLES
[0133] The present invention will be described in more detail below with reference to examples. The materials, amounts, ratios, processing contents, and processing procedures shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.
[0134] [Synthesis of monomer mA-1] The following monomer mA-1 was synthesized with reference to the examples of WO 2019 / 225632. [ka]
[0135] [Synthesis of monomer mA-2] The monomer mA-2 shown below was synthesized according to the following scheme. [ka]
[0136] [Synthesis of monomer mB-1c] Hydroxyethyl methacrylate (100.0 g) and dimethylacetamide (600 mL) were added to a 3 L three-neck flask equipped with a stirring blade, a thermometer, a dropping funnel, and a reflux condenser. Then, while stirring the resulting mixture at 0°C, 3-chloropropionic acid chloride (126.6 g) was added dropwise to the flask, and the mixture was allowed to react at room temperature for 3 hours. Ethyl acetate (1L) was added to the reaction solution, and the mixture was washed with 1N hydrochloric acid, saturated sodium bicarbonate water, ion-exchanged water, and saturated saline, and the organic phase was dried over magnesium sulfate. The magnesium sulfate was filtered off, and the organic phase was concentrated, and then purified with a silica gel column (hexane / ethyl acetate=3 / 1) to obtain 148.8 g of the monomer mB-1c shown below. [ka]
[0137] [Synthesis of photoalignable polymer A-1] A flask equipped with a condenser, a thermometer, and a stirrer was charged with 2-butanone (23 g), 1H,1H,7H-dodecafluoroheptyl methacrylate (1.9 g), monomer mA-1 (1.7 g), monomer mB-1c (6.9 g), and 2,2'-azobis(isobutyronitrile) (0.075 g). While flowing nitrogen into the flask at 15 mL / min, the resulting solution was stirred for 7 hours while maintaining the reflux state by heating in a water bath. After the reaction was completed, the reaction solution was allowed to cool to room temperature, and the resulting polymer solution was poured into a large excess of methanol to precipitate the polymer. The precipitate was then collected by filtration, and the collected solid was washed with a large amount of methanol, and then vacuum dried at 40°C for 6 hours to obtain a polymer A-1c represented by the following formula. [ka]
[0138] Next, 3.3 g of polymer A-1c, 4-methoxyphenol (0.016 g), triethylamine (3.75 g), and dimethylacetamide (4.95 g) were charged into a flask equipped with a condenser, a thermometer, and a stirrer, and the resulting solution was stirred at 60°C for 4 hours by heating in a water bath. After the reaction was completed, the reaction solution was allowed to cool to room temperature, and the resulting reaction solution was poured into a large excess of methanol / water (1 / 3) to precipitate the polymer. The precipitate was collected by filtration, washed with a large amount of methanol / water (1 / 3), and then dried by blowing air at 40°C for 12 hours to obtain the photoalignment polymer A-1 represented by the following formula. In addition, the numerical value shown for each repeating unit in the following structural formula indicates the content (mass%) of each repeating unit with respect to all repeating units, and in the following, the repeating units from the left side were 20 mass%, 18 mass%, and 62 mass%. The weight average molecular weight of the photoalignment polymer A-1 measured by the above-mentioned method was 56,000. [ka]
[0139] [Synthesis of photoalignable polymer A-2] In a flask equipped with a condenser, a thermometer, and a stirrer, 2-butanone (23 g), monomer mA-2 (1.8 g), monomer mB-1c (8.7 g), and 2,2'-azobis(isobutyronitrile) (0.075 g) were charged, and while flowing nitrogen into the flask at 15 mL / min, the resulting solution was stirred while maintaining a reflux state by heating in a water bath for 7 hours. After the reaction was completed, the reaction solution was allowed to cool to room temperature, and the resulting polymer solution was poured into a large excess of methanol to precipitate the polymer. The precipitate was then collected by filtration, and the collected solid was washed with a large amount of methanol, and then vacuum dried at 40°C for 6 hours to obtain a photoalignment polymer A-2c represented by the following formula. [ka]
[0140] Next, 3.3 g of polymer A-2c, 4-methoxyphenol (0.016 g), triethylamine (3.75 g), and dimethylacetamide (4.95 g) were charged into a flask equipped with a condenser, a thermometer, and a stirrer, and the resulting solution was stirred at 60° C. for 4 hours by heating in a water bath. After the reaction was completed, the reaction solution was allowed to cool to room temperature, and the resulting reaction solution was poured into a large excess of methanol / water (1 / 3) to precipitate the polymer. The precipitate was collected by filtration, washed with a large amount of methanol / water (1 / 3), and then dried by blowing air at 40°C for 12 hours to obtain the photoalignment polymer A-2 represented by the following formula. The numerical values shown for each repeating unit in the following structural formulas represent the content (mass %) of each repeating unit relative to all repeating units, and below, the repeating units on the left side were 20 mass % and 80 mass %. The weight average molecular weight of the photoalignment polymer A-2 measured by the above-mentioned method was 58,000. [ka]
[0141] [Synthesis of photoalignable polymer A-3] Photoalignment polymer A-3 was synthesized in the same manner as for photoalignment polymer A-1, except that the following monomer mC-1 was used instead of 1H,1H,7H-dodecafluoroheptyl methacrylate. In addition, the numerical value shown for each repeating unit in the following structural formula indicates the content (mass%) of each repeating unit with respect to all repeating units, and in the following, the repeating units from the left side were 20 mass%, 18 mass%, and 62 mass%. The weight average molecular weight of the photoalignment polymer A-3 measured by the above-mentioned method was 60,000. [ka] JPEG0007655931000032.jpg5061
[0142] [Synthesis of photoalignable polymer A-4] Photoalignment polymer A-4 was synthesized in the same manner as photoalignment polymer A-1, except that 1H,1H,7H-dodecafluoroheptyl methacrylate (6.0 g), monomer mA-1 (1.8 g), and monomer mB-1c (2.7 g) were used. In addition, the numerical values shown for each repeating unit in the following structural formulas represent the content (mass%) of each repeating unit relative to all repeating units, and in the following, the repeating units from the left were 60 mass%, 18 mass%, and 22 mass%. The weight average molecular weight of the photoalignment polymer A-4 measured by the above-mentioned method was 55,000. [ka]
[0143] [Synthesis of photoalignable polymer A-5] Photoalignment polymer A-5 was synthesized in the same manner as photoalignment polymer A-1, except that 1H,1H,7H-dodecafluoroheptyl methacrylate (0.5 g), monomer mA-1 (1.6 g), and monomer mB-1c (8.3 g) were used. In addition, the numerical value shown for each repeating unit in the following structural formula indicates the content (mass%) of each repeating unit relative to all repeating units, and in the following, the repeating units from the left were 5 mass%, 18 mass%, and 77 mass%. The weight average molecular weight of the photoalignment polymer A-5 measured by the above-mentioned method was 56,000. [ka]
[0144] [Synthesis of photoalignable polymer A-6] Photoalignment polymer A-6 was synthesized in the same manner as for photoalignment polymer A-1, except that 3,3,3-trifluoropropyl methacrylate (2.8 g), monomer mA-1 (1.7 g), and monomer mB-1c (5.9 g) were used. In addition, the numerical values shown for each repeating unit in the following structural formulas represent the content (mass%) of each repeating unit relative to all repeating units, and in the following, the repeating units from the left were 30 mass%, 18 mass%, and 52 mass%. The weight average molecular weight of the photoalignment polymer A-6 measured by the above-mentioned method was 57,000. [ka]
[0145] [Synthesis of photoalignable polymer A-7] Photoalignment polymer A-7 was synthesized in the same manner as for photoalignment polymer A-1, except that the following monomer mC-2 was used instead of 1H,1H,7H-dodecafluoroheptyl methacrylate. In addition, the numerical value shown for each repeating unit in the following structural formula indicates the content (mass%) of each repeating unit with respect to all repeating units, and in the following, the repeating units from the left side were 20 mass%, 18 mass%, and 62 mass%. The weight average molecular weight of the photoalignment polymer A-7 measured by the above-mentioned method was 59,000. [ka] JPEG0007655931000037.jpg5052
[0146] [Synthesis of photoalignable polymer A-8] The photoalignment polymer A-8 shown below was synthesized with reference to the method described in WO 2019 / 159707. The numerical values shown for each repeating unit in the following structural formulas represent the content (mass %) of each repeating unit relative to all repeating units, and in the following, the repeating units on the left side were 40 mass % and 60 mass %. The weight average molecular weight of the photoalignment polymer A-8 measured by the above-mentioned method was 61,000. [ka]
[0147] [Synthesis of photoalignable polymer A-9] The photoalignment polymer A-9 shown below was synthesized with reference to the method described in International Publication No. 2018 / 216812. In addition, the numerical values shown for each repeating unit in the following structural formulas represent the content (mass%) of each repeating unit relative to all repeating units, and in the following, the repeating units from the left are 30 mass%, 50 mass%, 15 mass%, and 5 mass%. The weight average molecular weight of the photoalignment polymer A-9 measured by the above-mentioned method was 57,000. [ka]
[0148] [Example 1] [Preparation of composition for forming second optically anisotropic layer] Composition 1 for forming a second optically anisotropic layer was prepared as follows. ------------------------------------------------------------------ Composition 1 for forming second optically anisotropic layer ------------------------------------------------------------------ 83.00 parts by weight of the following polymerizable liquid crystal compound L-1 15.00 parts by weight of the following polymerizable liquid crystal compound L-2 2.00 parts by weight of the following polymerizable liquid crystal compound L-3 Polymerizable monomer (A-400, manufactured by Shin-Nakamura Chemical Co., Ltd.) 4.00 parts by mass 5.00 parts by mass of the following polymerization initiator S-1 (oxime type) 2.00 parts by weight of the following polymer M-1 2.00 parts by weight of the following vertical alignment agent S01 2.00 parts by mass of the above photoalignment polymer A-1 Methyl ethyl ketone 41.20 parts by weight Methyl isobutyl ketone 610.50 parts by weight ------------------------------------------------------------------
[0149] Polymerizable liquid crystal compound L-1 [ka]
[0150] Polymerizable liquid crystal compound L-2 [ka]
[0151] Polymerizable liquid crystal compound L-3 [ka]
[0152] Polymerization initiator S-1 [ka]
[0153] Polymer M-1 [ka]
[0154] Vertical alignment agent S01 [ka]
[0155] [Formation of second optically anisotropic layer] The cellulose acylate film used was the same as that used in Example 6 of JP-A No. 2012-215689. Composition 1 prepared above was applied to one side of this film with a wire bar. Next, the sample was heated to 60°C for 1 minute with hot air, and then irradiated with a 365 nm UV-LED at a dose of 100 mJ / cm while purging with nitrogen to keep the oxygen concentration in the atmosphere at 100 ppm or less. 2 A precursor layer was formed by irradiating the film with ultraviolet light of 1000 nm. The obtained precursor layer was irradiated with UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYA) at room temperature through a wire grid polarizer at 7.9 mJ / cm. 2 By irradiating the film with light (wavelength: 313 nm), a second optically anisotropic layer having an alignment control ability was formed on the surface. The second optically anisotropic layer thus formed was an optically anisotropic layer that did not exhibit reverse wavelength dispersion, and was a positive C plate. The thickness of the second optically anisotropic layer thus formed was about 0.5 μm.
[0156] [Formation of the first optically anisotropic layer (upper layer)] Next, the second optically anisotropic layer was coated with the following composition 1 for forming a first optically anisotropic layer using a wire bar. The coating film formed on the second optically anisotropic layer was heated to 120°C with hot air, and then cooled to 60°C. After that, the coating was irradiated with a 365 nm UV-LED at a dose of 100 mJ / cm while purging with nitrogen to create an atmosphere with an oxygen concentration of 100 ppm or less. 2 The sample was then heated to 120°C and irradiated with ultraviolet light at a dose of 500 mJ / cm using an ultra-high pressure mercury lamp (UL750; manufactured by HOYA) while purging with nitrogen so that the oxygen concentration in the atmosphere was 100 ppm or less. 2 The coating film was irradiated with ultraviolet light (wavelength: 365 nm).By the above procedure, an optical laminate of Example 1 including a first optically anisotropic layer (film thickness: 2.9 μm) was produced. The first optically anisotropic layer thus formed was an optically anisotropic layer exhibiting reverse wavelength dispersion, and was a positive A plate. Furthermore, the obtained optical laminate had Re(550) derived from the first optically anisotropic layer of 140 nm, Re(450) / Re(550) of 0.82, and Re(650) / Re(550) of 1.04. ---------------------------------------------------------------------------------- Composition for forming first optically anisotropic layer 1 ------------------------------------------------------------------ 39.00 parts by weight of the following polymerizable liquid crystal compound L-4 39.00 parts by weight of the following polymerizable liquid crystal compound L-5 17.00 parts by mass of the polymerizable liquid crystal compound L-1 5.00 parts by weight of the following polymerizable compound A-1 0.50 parts by mass of the above polymerization initiator S-1 (oxime type) Leveling agent (compound T-1 below) 0.20 parts by weight Cyclopentanone 235.00 parts by mass ------------------------------------------------------------------
[0157] Polymerizable liquid crystal compound L-4 [ka]
[0158] Polymerizable liquid crystal compound L-5 [ka]
[0159] Polymerizable compound A-1 [ka]
[0160] Compound T-1 [ka]
[0161] [Example 2] An optical laminate was produced in the same manner as in Example 1, except that the photoalignable polymer A-1 in Example 1 was changed to the photoalignable polymer A-2.
[0162] [Example 3] An optical laminate was produced in the same manner as in Example 1, except that the photoalignable polymer A-1 in Example 1 was changed to the photoalignable polymer A-3.
[0163] [Example 4] An optical laminate was produced in the same manner as in Example 1, except that the photoalignable polymer A-1 in Example 1 was changed to the photoalignable polymer A-4.
[0164] [Example 5] An optical laminate was produced in the same manner as in Example 1, except that the photoalignable polymer A-1 in Example 1 was changed to the photoalignable polymer A-5.
[0165] [Example 6] An optical laminate was produced in the same manner as in Example 1, except that the photoalignable polymer A-1 in Example 1 was changed to the photoalignable polymer A-6.
[0166] [Example 7] An optical laminate was produced in the same manner as in Example 1, except that the first optically anisotropic layer-forming composition 1 in Example 1 was changed to the first optically anisotropic layer-forming composition 2 described below. The first optically anisotropic layer thus formed was an optically anisotropic layer exhibiting reverse wavelength dispersion, and was a positive A plate. Furthermore, the obtained optical laminate had Re(550) derived from the first optically anisotropic layer of 140 nm, Re(450) / Re(550) of 0.82, and Re(650) / Re(550) of 1.04. ------------------------------------------------------------------ Composition 2 for forming first optically anisotropic layer ------------------------------------------------------------------ 12.00 parts by weight of the following polymerizable liquid crystal compound L-6 Leveling agent (BYK-361N, manufactured by BYK-Chemie) 0.12 parts by mass Polymerization initiator (Irgacure 369, manufactured by BASF Japan) 0.72 parts by mass Cyclopentanone 100.00 parts by mass ------------------------------------------------------------------
[0167] Polymerizable liquid crystal compound L-6 [ka]
[0168] [Example 8] An optical laminate was produced in the same manner as in Example 1, except that the amount of the photoalignable polymer A-1 in the composition 1 for forming the second optically anisotropic layer in Example 1 was changed to 5.00 parts by mass.
[0169] [Example 9] An optical laminate was produced in the same manner as in Example 1, except that the amount of the photoalignable polymer A-1 in the composition 1 for forming the second optically anisotropic layer in Example 1 was changed to 15.00 parts by mass.
[0170] [Example 10] An optical laminate was produced in the same manner as in Example 1, except that the photoalignable polymer A-1 in Example 1 was changed to the photoalignable polymer A-7.
[0171] [Example 11] An optical laminate was produced in the same manner as in Example 1, except that the composition 1 for forming a second optically anisotropic layer in Example 1 was changed to the composition 2 for forming a second optically anisotropic layer described below. ------------------------------------------------------------------ Composition 2 for forming second optically anisotropic layer ------------------------------------------------------------------ The polymerizable liquid crystal compound L-1 83.00 parts by mass 15.00 parts by mass of the polymerizable liquid crystal compound L-2 2.00 parts by mass of the polymerizable liquid crystal compound L-3 Polymerizable monomer (A-400, manufactured by Shin-Nakamura Chemical Co., Ltd.) 4.00 parts by mass The above polymerization initiator S-1 (oxime type) 5.00 parts by mass 2.00 parts by mass of the above polymer M-1 2.00 parts by weight of the vertical alignment agent S01 2.00 parts by mass of the above photoalignment polymer A-1 0.20 parts by weight of the following surfactant B-1 (weight average molecular weight: 2200) Methyl ethyl ketone 41.20 parts by weight Methyl isobutyl ketone 610.50 parts by weight ------------------------------------------------------------------
[0172] Surfactant B-1 [ka]
[0173] [Comparative Example 1] An optical laminate was produced in the same manner as in Example 1, except that the photoalignable polymer A-1 in Example 1 was changed to the photoalignable polymer A-8.
[0174] [Comparative Example 2] An optical laminate was produced in the same manner as in Example 1, except that the formation of the second optically anisotropic layer in Example 1 was changed as follows.
[0175] [Preparation of composition for forming second optically anisotropic layer] Composition 3 for forming a second optically anisotropic layer was prepared as follows. ------------------------------------------------------------------ Composition 3 for forming second optically anisotropic layer ------------------------------------------------------------------ The polymerizable liquid crystal compound L-1 83.00 parts by mass 15.00 parts by mass of the polymerizable liquid crystal compound L-2 2.00 parts by mass of the polymerizable liquid crystal compound L-3 Polymerizable monomer (A-400, manufactured by Shin-Nakamura Chemical Co., Ltd.) 4.00 parts by mass The above polymerization initiator S-1 (oxime type) 5.00 parts by mass 3.00 parts by weight of the following photoacid generator D-1 2.00 parts by mass of the above polymer M-1 2.00 parts by weight of the vertical alignment agent S01 2.00 parts by mass of the above photoalignment polymer A-9 Methyl ethyl ketone 42.30 parts by weight Methyl isobutyl ketone 627.50 parts by weight ------------------------------------------------------------------
[0176] Photoacid generator D-1 [ka]
[0177] [Formation of second optically anisotropic layer] The cellulose acylate film used was the same as that used in Example 6 of JP 2012-215689 A. The composition 2 prepared above was applied to one side of this film using a #3.0 wire bar. Heat the sample to 60°C for 1 minute with hot air, and then purge with nitrogen to keep the oxygen concentration below 100 ppm. Using a 365 nm UV-LED, irradiate the sample at a dose of 100 mJ / cm. 2 After that, it was annealed with hot air at 120°C for 1 minute to form a precursor layer. The obtained precursor layer was irradiated with UV light (ultra-high pressure mercury lamp; UL750; manufactured by HOYA) at room temperature through a wire grid polarizer at 7.9 mJ / cm. 2 By irradiating the film with light (wavelength: 313 nm), a second optically anisotropic layer having an alignment control ability was formed on the surface. The second optically anisotropic layer thus formed was an optically anisotropic layer that did not exhibit reverse wavelength dispersion, and was a positive C plate. The thickness of the second optically anisotropic layer thus formed was about 0.5 μm.
[0178] [Comparative Example 3] An optical laminate was produced in the same manner as in Example 7, except that the photoalignable polymer A-1 in Example 7 was changed to the photoalignable polymer A-8.
[0179] [Comparative Example 4] An optical laminate was produced in the same manner as in Comparative Example 2, except that the composition 1 for forming a first optically anisotropic layer in Comparative Example 2 was changed to the composition 2 for forming a first optically anisotropic layer.
[0180] For the optical laminates obtained in Examples 1 to 11 and Comparative Examples 1 to 4, the presence or absence of a photo-aligned polymer on the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer (hereinafter, in this paragraph and Table 4 below, abbreviated as "interface") was confirmed by the above-mentioned method, and the element ratio of fluorine or silicon at the interface was measured. The measurement results are shown in Table 4 below. In Table 4 below, for Comparative Examples 2 and 4 in which photoalignment polymer A-9 was used, the presence or absence of photoalignment polymer at the interface is evaluated as "present." However, in the case of photoalignment polymer A-9 synthesized by the method described in International Publication No. 2018 / 216812, the cleavable group is decomposed and the fluorine atom or silicon atom is volatilized during the formation of the second optically anisotropic layer, so that a photoalignment polymer having a photoalignment group is present at the interface, but a photoalignment polymer having a photoalignment group and a fluorine atom or silicon atom is not present at the interface.
[0181] [Moist heat durability] From each of the optical laminates obtained in Examples 1 to 11 and Comparative Examples 1 to 4, a square film with a side length of 40 mm was cut out. An adhesive was applied to the surface of the obtained film on the side of the first optically anisotropic layer, and the adhesive surface was attached to a piece of glass of the same size as the film, and then the film substrate was peeled off (the first and second optically anisotropic layers were transferred). The obtained square laminate with a side length of 40 mm was kept in an environment of a temperature of 100° C. and a humidity of 95% for 144 hours, and then Re(550) (in-plane retardation at a wavelength of 550 nm) was measured and evaluated according to the following criteria. The results are shown in Table 4 below. In addition, since the optically anisotropic layer that has a significant effect on the measurement results of Re(550) is a positive A plate, the evaluation based on the following criteria can be said to be an evaluation of the wet and heat durability of the optically anisotropic layer that exhibits reverse wavelength dispersion. A: When the ratio of Re(550) after holding in an environment with a temperature of 100°C and humidity of 95% is 98% or more compared to the Re(550) before holding B: When the ratio of Re(550) after holding in an environment with a temperature of 100°C and humidity of 95% is 96% or more and less than 98% of the Re(550) before holding C: When the ratio of Re(550) after exposure to an environment of 100°C and 95% humidity is less than 96% of the Re(550) before exposure
[0182] [Adhesion] The adhesion between the first and second optically anisotropic layers was evaluated by a cross-cut test (cross-cut method) according to the following specific procedure. First, the first optically anisotropic layer side of the optical laminates obtained in Examples 1 to 11 and Comparative Examples 1 to 4 was treated once using a corona treatment device under conditions of an output of 0.3 kW and a treatment speed of 7.6 m / min. Next, the film was cut into a square shape with each side measuring 40 mm. An adhesive was applied to the surface of the first optically anisotropic layer of the obtained film, and the adhesive surface was attached to a piece of glass of the same size as the film, and then the film substrate was peeled off (the first and second optically anisotropic layers were transferred). Next, 11 cuts were made at 1 mm intervals on the surface of the second optically anisotropic layer using a cutter knife and a cutter guide to create 100 grids. Cellophane tape (registered trademark) was pressed onto the grids and then peeled off, and this operation was repeated three times in total, with the Cellophane tape (registered trademark) replaced with a new one each time. Thereafter, the state of the grids was observed, and the number of grids from which the second optically anisotropic layer had peeled off was counted. The number of peeled grids was evaluated according to the following evaluation criteria. In any case, peeling did not occur between the adhesive and the first optically anisotropic layer. The results are shown in Table 4 below. A: 0 grids peeled off B: 1 to 5 grids peeled off C: Five or more grids peeled off
[0183] [Table 4]
[0184] The results shown in Table 4 reveal that when the atomic ratio of fluorine or silicon on the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer is greater than 15.00 atomic %, the adhesion between the first optically anisotropic layer and the second optically anisotropic layer is poor (Comparative Examples 1 and 3). In addition, when photo-oriented polymer A-8 synthesized by the method described in International Publication No. 2018 / 216812 was used, the elemental ratio of fluorine or silicon on the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer was 0 atomic %, and it was found that the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion was poor (Comparative Examples 2 and 4).
[0185] In contrast, it was found that when a photo-alignable polymer is present on the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer so that the atomic ratio of fluorine or silicon is 0.05 to 15.00 atomic %, the optically anisotropic layer exhibiting reverse wavelength dispersion has good humidity and heat durability, and the adhesion between the first optically anisotropic layer and the second optically anisotropic layer is also good (Examples 1 to 11). Furthermore, a comparison between Examples 1 and 2 revealed that the same effect can be obtained whether the photo-alignable polymer is a polymer having a repeating unit containing a fluorine atom or a silicon atom in addition to a photo-alignable group, or a copolymer having a repeating unit containing a photo-alignable group and a repeating unit containing a fluorine atom or a silicon atom. Furthermore, by comparing Examples 1 and 2 with Example 3, it was found that the use of a photoalignment polymer having a photoalignment group and a fluorine atom resulted in better wet heat durability of an optically anisotropic layer exhibiting reverse wavelength dispersion than a photoalignment polymer having a photoalignment group and a silicon atom. Furthermore, by comparing Example 1 and Example 6, it was found that when the photoalignable polymer has a partial structure represented by the above formula (1), the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion properties is improved. Furthermore, a comparison of Examples 1, 8 and 9 revealed that when the atomic ratio of fluorine or silicon on the surface of the second optically anisotropic layer in contact with the first optically anisotropic layer is 0.20 to 8.00 atomic %, a good balance is achieved between the wet heat durability of the optically anisotropic layer exhibiting reverse wavelength dispersion and the adhesion between the first optically anisotropic layer and the second optically anisotropic layer. Moreover, from the results of Example 11, it was found that even when a highly elutable surfactant was blended in the composition for forming the second optically anisotropic layer, results equivalent to those of Example 1 were obtained.
Claims
1. An optical laminate in which a first optically anisotropic layer and a second optically anisotropic layer are directly laminated, the first optically anisotropic layer and the second optically anisotropic layer are both made of liquid crystal layers, At least one of the first optically anisotropic layer and the second optically anisotropic layer exhibits reverse wavelength dispersion, a photoalignment polymer having a photoalignment group and a fluorine atom or a silicon atom is present on a surface of the second optically anisotropic layer on the side in contact with the first optically anisotropic layer, an element ratio of fluorine or silicon in the surface of the second optically anisotropic layer on the side in contact with the first optically anisotropic layer is 0.05 to 15.00 atomic %;
2. The optical laminate according to claim 1 , wherein the photo-alignable group is a photo-alignable group that undergoes at least one of dimerization and isomerization by the action of light.
3. The optical laminate according to claim 1 or 2, wherein the photoalignable group is selected from the group consisting of a cinnamoyl group, an azobenzene group, a chalconyl group, and a coumarin group.
4. The optical laminate according to any one of claims 1 to 3, wherein the photoalignable polymer has a repeating unit represented by the following formula (A): 【Chemistry 1】 Here, in the formula (A), R A1 represents a hydrogen atom or a substituent. L A1 represents a single bond or a divalent linking group. R A2 , R A3 , R A4 , R A5 and R A6 Each of R independently represents a hydrogen atom or a substituent. A2 , R A3 , R A4 , R A5 and R A6 Among these, two adjacent groups may be bonded to form a ring.
5. The optical laminate according to any one of claims 1 to 4, wherein the photoalignable polymer has a partial structure represented by the following formula (1): *-(CF 2 ) m -* ・・・(1) In the formula (1), * represents a bonding position, and m represents an integer of 2 to 20.
6. The optical laminate according to any one of claims 1 to 5, wherein the photo-aligned polymer has a group represented by the following formula (2): *-(CF 2 ) m -X ・・・(2) In the formula (2), * represents a bonding position, m represents an integer of 2 to 20, and X represents a hydrogen atom or a fluorine atom.
7. The optical laminate according to claim 6, wherein X in the formula (2) represents a hydrogen atom.
8. The optical laminate according to any one of claims 1 to 4, wherein the photo-aligned polymer has a group represented by the following formula (3): *-C(Y)(CF 3 ) 2 ・・・(3) In the formula (3), * represents a bonding position, and Y represents a hydrogen atom or a substituent.
9. The optical laminate according to any one of claims 1 to 8, wherein at least one of the first optically anisotropic layer and the second optically anisotropic layer is an optically anisotropic layer in which the orientation of a liquid crystal compound having any one of aromatic rings selected from the group consisting of groups represented by the following formulas (Ar-1) to (Ar-7) is fixed: 【Chemistry 2】 In the formulas (Ar-1) to (Ar-7), * indicates the bond position. Q 1 represents N or CH. Q 2 is -S-, -O-, or -N(R 6 )-, R 6 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. Y 1 represents an aromatic hydrocarbon group having 6 to 12 carbon atoms which may have a substituent, an aromatic heterocyclic group having 3 to 12 carbon atoms which may have a substituent, or an alicyclic hydrocarbon group having 6 to 20 carbon atoms which may have a substituent, and -CH 2 One or more of - may be substituted by -O-, -S- or -NH-. Z 1 , Z 2 and Z 3 each independently represents a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, a monovalent alicyclic hydrocarbon group having 3 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a monovalent aromatic heterocyclic group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -OR 7 , -NR 8 R 9 , -SR 10 , -COOR 11 or -COR 12 represents R 7 ~R 12 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; Z 1 and Z 2 may be bonded to each other to form an aromatic ring. A 3 and A 4 Each independently represents -O-, -N(R 13 ) represents a group selected from the group consisting of -, -S-, and -CO-; R 13 represents a hydrogen atom or a substituent. X represents a hydrogen atom or a nonmetallic atom of Groups 14 to 16 which may have a substituent bonded thereto. D 7 and D. 8 each independently represents a single bond, -CO-, -O-, -S-, -C(=S)-, or -CR 1 R 2 -, -CR 3 =CR 4 --, --NR 5 -, or a divalent linking group consisting of two or more of these, R 1 ~R 5 each independently represents a hydrogen atom, a fluorine atom, or an alkyl group having 1 to 12 carbon atoms. SP 3 and S.P. 4 each independently represents a single bond, a linear or branched alkylene group having 1 to 12 carbon atoms, or —CH 2 represents a divalent linking group in which one or more -'s are substituted with -O-, -S-, -NH-, -N(Q)-, or -CO-, and Q represents a substituent. L 3 and L 4 each independently represents a monovalent organic group. Ax represents an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocycles. Ay represents a hydrogen atom, an alkyl group having 1 to 12 carbon atoms which may have a substituent, or an organic group having 2 to 30 carbon atoms and having at least one aromatic ring selected from the group consisting of aromatic hydrocarbon rings and aromatic heterocycles. The aromatic rings in Ax and Ay may have a substituent, and Ax and Ay may be bonded to form a ring. Q 3 represents a hydrogen atom or an optionally substituted alkyl group having 1 to 20 carbon atoms.
10. The optical laminate according to any one of claims 1 to 9, wherein the first optically anisotropic layer is a positive A plate.
11. The optical laminate according to any one of claims 1 to 10, wherein the second optically anisotropic layer is a positive C plate.
12. A photo-aligning polymer having a photo-aligning group and a silicon atom is present on a surface of the second optically anisotropic layer in contact with the first optically anisotropic layer, 2. The optical laminate according to claim 1, wherein the element ratio of silicon in the surface of the second optically anisotropic layer that contacts the first optically anisotropic layer is 0.05 to 15.00 atomic %.
13. A polarizing plate comprising the optical laminate according to any one of claims 1 to 12 and a polarizer.
14. An image display device comprising the optical laminate according to any one of claims 1 to 12 or the polarizing plate according to claim 13.
Citation Information
Patent Citations
Laminated phase difference layer, its manufacturing method and liquid crystal display device using phase difference layer
JP2004326089A
mask
JP2015507214A
Optical film, polarizing plate, and production method of optical film
JP2016053709A
Optical film
JP2017097331A
Method for producing alignment on liquid crystal polymer materials - Patent Application 20070122997
JP2019522245A
Cited By
Optical laminate, polarizing plate, and image device display
US12736729B2